Novel zeolite, method for preparing the zeolite and use of the zeolite for converting aromatic hydrocarbons

By using a new MEL skeleton type zeolite with small crystalline size as a catalyst, the isomerization method of C8 aromatic hydrocarbons is solved in the prior art, and the problems of high loss and low selectivity in the isomerization process of xylene in the prior art are achieved, and the efficient and low loss isomerization effect is achieved.

CN113646287BActive Publication Date: 2025-04-25EXXONMOBIL CHEMICAL PATENTS INC
View PDF 43 Cites 0 Cited by

Patent Information

Application Number
CN202080025466.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-07-11
Filing Date
2020-03-25
Publication Date
2025-04-25
Estimated Expiration
2040-03-25

AI Technical Summary

Technical Problem

The prior art has problems such as high xylene loss, high toluene and benzene yields in the isomerization process of xylene, and it is difficult to achieve high paraxylene selectivity under high-heavy time-space speed.

Method used

A novel MEL skeleton type zeolite with small crystalline size is used as catalyst to improve catalytic activity and reduce xylene loss by operating the isomerization method of C8 aromatic hydrocarbons in the liquid phase.

Benefits of technology

High isomerization activity, low xylene loss, low toluene and benzene yields, and high paraxylene selectivity are achieved, especially showing significant advantages at high weight time-space velocity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003283816680000031
    Figure BDA0003283816680000031
  • Figure BDA0003283816680000041
    Figure BDA0003283816680000041
  • Figure BDA0003283816680000461
    Figure BDA0003283816680000461
Patent Text Reader

Abstract

Novel MEL framework type zeolites can be prepared to have small crystallite sizes and desired silica / SiO2 molar ratios. Catalyst compositions comprising such MEL framework type zeolites can be particularly advantageous in isomerizing C8 aromatic mixtures. Isomerization processes for converting C8 aromatic hydrocarbons can advantageously utilize catalyst compositions comprising MEL framework type zeolites.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Inventors: Paul Podsiadlo, Eric D. Metzger, Wenyih Frank Lai, Ali A. Kheir, Dominick A. Zurlo, Jocelyn A. Gilcrest, Kathleen M. Keville

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS

[0003] This application claims priority to and the benefit of U.S. Provisional Application No. 62 / 826,317, filed on March 29, 2019, and European Patent Application No. 19185757.2, filed on July 11, 2019, the disclosures of which are incorporated herein by reference. Technical Field

[0004] The present disclosure relates to zeolitic materials, methods for their preparation and their use in aromatic hydrocarbon conversion. In particular, the present disclosure relates to MEL framework type zeolitic materials, methods for their manufacture and their use in isomerizing C8 aromatic hydrocarbons. The present disclosure can be used, for example, in a method for preparing xylenes, especially para-xylene, comprising the step of isomerizing a mixture of C8 aromatic hydrocarbons in the presence of an isomerization catalyst, especially in the liquid phase. Background Art

[0005] A high purity p-xylene product is generally produced by separating p-xylene from a p-xylene-rich aromatic hydrocarbon mixture containing p-xylene, o-xylene, m-xylene, and optionally, EB in a p-xylene separation / recovery system. The p-xylene recovery system may include, for example, a crystallizer and / or an adsorption chromatography separation system known in the prior art. The p-xylene-poor stream produced by the p-xylene recovery system (the "filtrate" from the crystallizer when separating p-xylene crystals, or the "raffinate" from the adsorption chromatography separation system, collectively referred to as "raffinate" in the present disclosure) is rich in m-xylene and o-xylene, and contains p-xylene at a concentration generally lower than its concentration in an equilibrium mixture consisting of m-xylene, o-xylene, and p-xylene. In order to increase the yield of p-xylene, the raffinate stream may be fed to an isomerization unit, wherein the xylene undergoes an isomerization reaction in a contact isomerization catalyst system to produce an isomerization effluent rich in p-xylene compared to the raffinate. At least a portion of the isomerization effluent may be recycled to the para-xylene recovery system, forming a "xylenes loop", after optional separation and removal of light hydrocarbons that may be produced in the isomerization unit.

[0006] Xylene isomerization can be carried out under conditions where the C8 aromatics are substantially in the vapor phase in the presence of an isomerization catalyst (vapor phase isomerization, or "VPI").

[0007] A new generation of technology has been developed to allow the isomerization of xylenes at significantly lower temperatures in the presence of an isomerization catalyst, with the C8 aromatics being substantially in the liquid phase (liquid phase isomerization, or "LPI"). The use of LPI relative to conventional VPI can reduce the number of phase changes (liquid to vapor / vapor to liquid) required to process C8 aromatic feeds. This provides a sustainability advantage to the process in the form of significant energy savings. For any paraxylene production unit, it would be highly advantageous to deploy an LPI unit in addition to or in place of a VPI unit. For existing paraxylene production facilities that lack LPI, it would be highly advantageous to add an LPI unit to supplement the VPI unit or to replace the VPI unit.

[0008] Exemplary LPI processes and catalyst systems useful therefor are described in U.S. Patent Application Publication Nos. 2011 / 0263918 and 2011 / 0319688, 2017 / 0297977, 2016 / 0257631, and U.S. Patent No. 9,890,094, the contents of which are incorporated herein by reference in their entirety. In the LPI processes described in these references, MFI framework type zeolites (e.g., ZSM-5) are typically used as catalysts.

[0009] Because of the many advantages of the LPI process and the need to deploy this technology, there is also a need to improve this technology, particularly the catalysts used. The present disclosure satisfies this need and others.

[0010] References cited in the disclosure statement (37 CFR 1.97(h)): WO2000 / 010944; US5,689,027; US6,504,072; US6,689,929; USPub.No.2002 / 0082462 A1; US ​​Publication No.2014 / 0350316 A1; US ​​Publication No.2015 / 0376086 A1; US ​​Publication No.2015 / 0376087 A1; US ​​Publication No.2016 / 0101405 A1; US ​​Publication No.2016 / 0185686 A1; US ​​Publication No.2016 / 0264495 A1; US ​​Publication No.2017 / 0210683 A1; U.S. Patent Application Publication Nos. 2011 / 0263918; 2011 / 0319688; 2017 / 0297977 and 2016 / 0257631; US9,738,573; US9,708,233; US9,434,661; US9,321,029; US9,302,953; US9,295,970; US9,249,068; US9,227,891; US9,205,401; US9,156,749; US9,012,711; US7,915,471; and U.S. Patent Nos. 9,890,094 and 10,010,878; US6,448,459; U.S. Publication No. 2017 / 0204024 A1. Summary of the invention

[0011] It has been found in a surprising manner that a new class of MEL framework-type zeolites with very small crystallite sizes can be prepared. When used as a catalyst in a C8 aromatic isomerization process operating in a liquid phase ("LPI"), the new class of MEL framework-type zeolites exhibits surprisingly high performance. This high performance includes one or more of high isomerization activity, low xylene loss, low toluene yield, low benzene yield, low C9+ aromatic compound yield, and high para-xylene selectivity, particularly when compared to a similar liquid phase isomerization process using ZSM-5 zeolite as a catalyst. Very surprisingly, the high isomerization activity of this new class of MEL framework-type zeolites enables isomerization at extremely high weight hourly space velocities ("WHSV"), such as 5 h -1 (and even 10 hours -1 ) and higher, e.g., at ≥10 hours -1 Under, such as in even 15 hours -1 Effective and efficient LPI of C8 aromatics is achieved.

[0012] Accordingly, a first aspect of the present disclosure relates to a MEL framework-type zeolitic material comprising a plurality of crystallites, wherein at least 75% of the crystallites have a crystallite size of at most 200 nanometers, preferably at most 150 nanometers, preferably at most 100 nanometers, and more preferably at most 50 nanometers as determined by transmission electron microscopy image analysis.

[0013] A second aspect of the present disclosure relates to a method for preparing any zeolite material according to the first aspect of the present disclosure, the method comprising: (I) forming a synthesis mixture from a silicon source, an aluminum source, an alkali metal (M) hydroxide, a structure directing agent (SDA) source selected from the group consisting of tetrabutylammonium ("TBA") compounds, alkyl diamines containing 7 to 12 carbon atoms, and mixtures and combinations thereof, water, and optionally seed crystals, wherein the synthesis mixture has an overall composition in the following molar ratios:

[0014]

[0015]

[0016] (II) subjecting the synthesis mixture to crystallization conditions comprising heating the synthesis mixture at a temperature of 100°C to 150°C to form a reaction mixture comprising a solid material; and (III) obtaining a zeolitic material from the reaction mixture.

[0017] A third aspect of the present disclosure relates to a catalyst composition comprising any zeolite material according to the first aspect of the present disclosure.

[0018] A fourth aspect of the present disclosure relates to a method for converting a feed comprising C8 aromatic hydrocarbons, the method comprising: (I) feeding the aromatic hydrocarbon feed into a conversion reactor; and (II) contacting at least a portion of the C8 aromatic hydrocarbons in a liquid phase with a conversion catalyst composition comprising a MEL framework-type zeolite under conversion conditions to isomerize at least a portion of the C8 aromatic hydrocarbons to produce a conversion product effluent.

[0019] A fifth aspect of the present disclosure relates to a conversion method for a feed comprising C8 aromatic hydrocarbons, the method comprising: (I) supplying the aromatic hydrocarbon feed into a conversion reactor; and (II) contacting the C8 aromatic hydrocarbons substantially in a liquid phase with a catalyst composition of any one of items B1-B9 in a conversion reactor under conversion conditions to achieve isomerization of at least a portion of the C8 aromatic hydrocarbons to produce a conversion product effluent, wherein the conversion conditions include an absolute pressure sufficient to maintain the C8 hydrocarbons in the liquid phase, a temperature of 150-300°C, and a WHSV of 2.5-15. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In the attached picture:

[0021] Figure 1 , 2 3 are an X-ray diffraction ("XRD") pattern, a scanning electron microscope ("SEM") image, and a transmission electron microscope ("TEM") image, respectively, of the ZSM-11 zeolite synthesized in Example A1 of the present disclosure.

[0022] Figure 4 , 5 6 are the XRD pattern, SEM image and TEM image of the ZSM-11 zeolite synthesized in Example A2 of the present disclosure, respectively.

[0023] Figure 7 , 8 9 are the XRD pattern, SEM image and TEM image of the ZSM-11 zeolite synthesized in Example A3 of the present disclosure, respectively.

[0024] Fig.10 is a graph showing para-xylene selectivity as a function of WHSV in an exemplary process of the present disclosure.

[0025] Fig.11 It is displayed in Fig.10 A graph of A9+ yield as a function of WHSV for the same exemplary process is shown.

[0026] Fig.12 It is displayed in Fig.10 and 11 A graph of xylene loss as a function of WHSV for the same exemplary process is shown.

[0027] Detailed Description

[0028] In the present disclosure, a method is described as including at least one "step", it being understood that each step is an action or operation that can be performed one or more times in a method in a continuous or discontinuous manner. Unless otherwise specified or the context clearly indicates otherwise, the multiple steps in the method can be performed in the order in which they are listed, with or without overlap with one or more other steps, or in any other order, as the case may be. In addition, one or more, or even all steps can be performed simultaneously in terms of the same or different batches of materials. For example, in a continuous method, although the first step in the method is being performed on a raw material that has just been fed into the starting point of the method, the second step can be performed simultaneously on an intermediate product produced by processing the raw material that was fed into the method at an early stage in the first step. Preferably, these steps are performed in the described order.

[0029] Unless otherwise stated, all numerals representing quantities in this disclosure are to be understood as being modified by the term "approximately" in all cases. It should also be understood that the numerical values ​​used in the specification and claims constitute specific embodiments. Efforts have been made to ensure the accuracy of the data in the examples. However, it should be understood that any measurement data inherently contain a certain level of error due to the limitations of the techniques and equipment used to perform the measurements.

[0030] As used herein, the indefinite article "a" or "an" shall mean "at least one", unless specified to the contrary or the context clearly indicates otherwise. Thus, embodiments using "ether" include embodiments in which one, two or more ethers are used, unless otherwise specified or the context clearly indicates that only one ether is used.

[0031] As used herein, "consisting essentially of" means that the composition, feed or effluent comprises a given component in a concentration of at least 60 wt%, preferably at least 70 wt%, more preferably at least 80 wt%, more preferably at least 90 wt%, and still more preferably at least 95 wt%, based on the total weight of the composition, feed or effluent in question.

[0032] "Crystallite" refers to a grain of a material. Crystallites having microscopic or nanometer dimensions can be observed using a microscope such as a transmission electron microscope ("TEM"), a scanning electron microscope ("SEM"), a reflection electron microscope ("REM"), a scanning transmission electron microscope ("STEM"), etc. Crystallites can aggregate to form a polycrystalline material.

[0033] For purposes of this disclosure, the nomenclature of the elements is according to the version of the Periodic Table of the Elements described in Chemical and Engineering News, 63(5), p. 27 (1985).

[0034] The term "hydrocarbon" refers to (i) any compound consisting of hydrogen and carbon atoms or (ii) any mixture of two or more such compounds in (i).

[0035] The term "Cn hydrocarbon", where n is a positive integer, refers to (i) any hydrocarbon compound that contains a total of n carbon atoms (one or more) in its molecule, or (ii) any mixture of two or more such hydrocarbon compounds in (i). Thus, C2 hydrocarbons can be ethane, ethylene, acetylene, or any mixture of at least two of them in any proportion. "Cm to Cn hydrocarbon" or "Cm-Cn hydrocarbon", where m and n are positive integers and m < n, refers to any one of Cm, Cm+1, Cm+2, …, Cn-1, Cn hydrocarbons, or any mixture of two or more of them. Thus, "C2 to C3 hydrocarbons" or "C2-C3 hydrocarbons" can be any one of ethane, ethylene, acetylene, propane, propylene, propyne, allene, cyclopropane, and any mixture of two or more of them in any proportion between and among the components. "Saturated C2-C3 hydrocarbons" can be ethane, propane, cyclopropane, or any mixture of two or more of them in any proportion. "Cn+ hydrocarbon" refers to (i) any hydrocarbon compound that contains a total of at least n carbon atoms in its molecule, or (ii) any mixture of two or more such hydrocarbon compounds in (i). "Cn- hydrocarbon" refers to (i) any hydrocarbon compound that contains a total of at most n carbon atoms in its molecule, or (ii) any mixture of two or more such hydrocarbon compounds in (i). "Cm hydrocarbon stream" refers to a hydrocarbon stream that consists essentially of Cm hydrocarbon(s). "Cm-Cn hydrocarbon stream" refers to a hydrocarbon stream that consists essentially of Cm-Cn hydrocarbon(s).

[0036] The present disclosure provides a novel class of MEL framework type zeolite materials, methods for their preparation, and their use in the conversion of aromatic hydrocarbons such as the isomerization of C8 aromatic hydrocarbons. The present disclosure also relates to a method for converting aromatic hydrocarbons in the presence of a novel class of MEL framework type zeolite materials, such as an isomerization method for converting a C8 aromatic mixture, particularly an isomerization method operating in the liquid phase.

[0037] I. Novel class of MEL zeolite materials of the first aspect of the present disclosure

[0038] The novel class of MEL framework type zeolite materials of the first aspect of the present disclosure comprises a plurality of primary microcrystals. At least 75% (e.g., ≥80%, ≥85%, ≥90% or even ≥95%) of the microcrystals have a microcrystal size of ≤200 nanometers (e.g., ≤150, ≤100, ≤80, ≤50, ≤30 nanometers). Thus, for example, at least 75% (e.g., ≥80%, ≥85%, ≥90% or even ≥95%) of the microcrystals can have a microcrystal size in the range of cs1 to cs2 nanometers, where cs1 and cs2 can independently be 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 120, 140, 150, 160, 180, 200, provided that cs1 < cs2. Preferably, cs1 = 10 and cs2 = 150. More preferably, cs1 = 10 and cs2 = 50. In the present disclosure, the microcrystal size is defined as the maximum size of the microcrystals observed under a transmission electron microscope ("TEM"). To determine the microcrystal size, a sample of the zeolite material is placed in the TEM and an image of the sample is taken. The image is then analyzed to determine the microcrystal size and its distribution. The small microcrystal size of the MEL framework type zeolite materials of the present disclosure results in surprisingly high catalytic activity and other properties, as discussed and demonstrated below.

[0039] The microcrystals of the MEL framework type zeolite materials of the present disclosure can adopt various shapes, such as substantially spherical, rod-like, etc. The microcrystals can have an irregular shape in the TEM image. Thus, the microcrystals can exhibit a longest dimension ("primary dimension") in a first direction and a width ("secondary dimension") in another direction perpendicular to the first direction, where the width is defined as the dimension in the middle of the primary dimension, as determined by TEM image analysis. The ratio of the primary dimension to the width is called the aspect ratio of the microcrystals. In certain embodiments, the microcrystals can have an average aspect ratio in the range of ar1 to ar2 as determined by TEM image analysis, where ar1 and ar2 can independently be, for example, 1, 1.2, 1.4, 1.5, 1.6, 1.8, 2.0, 2.2, 2.4, 2.5, 2.6, 2.8, 3.0, 3.2, 3.4, 3.5, 3.6, 3.8, 4.0, 4.2, 4.4, 4.5, 4.6, 4.7, 4.8 and 5.0, provided that ar1 < ar2. In certain embodiments, preferably, ar1 = 1 and ar2 = 3. In certain embodiments, preferably, ar1 = 1 and ar2 = 2.

[0040] The primary microcrystals can have a narrow particle size distribution such that at least 90% by number of the primary microcrystals have a primary microcrystal size in the range of 10 to 80 nm, preferably in the range of 20 to 50 nm, as determined by analyzing the images of the primary microcrystals taken by TEM.

[0041] The small crystallites of the MEL framework type zeolite material of the present disclosure can aggregate to form agglomerates. Agglomerates are polycrystalline materials with void spaces at the crystallite boundaries. The MEL framework type zeolite of the present disclosure can comprise agglomerates, typically irregular agglomerates. Agglomerates are formed by primary crystallites, which may have an average primary crystallite size of less than 80 nm, preferably less than 70 nm, and more preferably less than 60 nm, for example less than 50 nm, as determined by TEM image analysis.

[0042] Optionally, the primary crystallites of the MEL framework-type zeolite may have an average primary crystallite size in each of the a, b and c crystallographic vectors as measured by X-ray diffraction of less than 80 nm, preferably less than 70 nm, in some cases less than 60 nm. The primary crystallites may optionally have an average primary crystallite size in each of the a, b and c crystallographic vectors as measured by X-ray diffraction of greater than 20 nm, optionally greater than 30 nm.

[0043] The MEL framework type zeolite of the present disclosure may include agglomerates of primary crystallites together with a mixture of some unagglomerated primary crystallites. Most of the MEL framework type zeolites, for example, can exist as agglomerates of primary crystallites greater than 50wt% or greater than 80wt%. Agglomerates can be regular or irregular forms. For more information about agglomerates, see Walter, D. (2013) Primary Particles-Aglomerates-Agregates, Nanomaterials (Deutsche Forschungsgemeinschaft (DFG) ed.), Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, Germany. DOI: 10.1002 / 9783527673919, pp. 1-24.

[0044] Optionally, the MEL framework type zeolite of the present disclosure may contain ≥50 wt%, preferably ≥70 wt%, advantageously ≥80 wt%, and more preferably ≥90 wt% of said irregular agglomerates, and optionally, it consists essentially of said irregular agglomerates, said irregular agglomerates being composed of primary microcrystals, said primary microcrystals having a primary microcrystal size of ≤200 nm, preferably ≤180 nm, preferably ≤150 nm, preferably ≤120 nm, preferably ≤100 nm, preferably ≤80 nm, preferably ≤70 nm, preferably ≤60 nm, preferably ≤50 nm, such as ≤30 nm. Preferably, the MEL framework type zeolite of the present disclosure contains less than 10 wt% of primary microcrystals with a size >200 nm as determined by TEM image analysis. Preferably, the MEL framework type zeolite of the present disclosure contains less than 10 wt% of primary microcrystals with a size >150 nm as determined by TEM image analysis. Preferably, the MEL framework type zeolite of the present disclosure contains less than 10 wt% of primary microcrystals with a size >100 nm as determined by TEM image analysis. Preferably, the MEL framework type zeolite of the present disclosure contains less than 10 wt% of primary microcrystals with a size >80 nm as determined by TEM image analysis.

[0045] Preferably, the primary microcrystals of the MEL framework type zeolite of the first and second aspects of the present disclosure have an aspect ratio of less than 3.0, and more preferably less than 2.0.

[0046] The agglomerates of the primary microcrystals generally have an irregular form in TEM images and can be referred to as "secondary" particles because they are formed from agglomerates of microcrystals that are "primary" particles.

[0047] In certain embodiments, the MEL framework type zeolite material of the present disclosure may have a silica to alumina ratio R(s / a) that can vary from r1 to r2, where r1 and r2 can independently be, for example, 10, 12, 14, 15, 16, 18, 20, 22, 24, 25, 26, 28, 30, 32, 34, 35, 36, 38, 40, 42, 44, 45, 46, 48, 50, 52, 54, 55, 56, 58, 60, provided that r1 < r2. In certain embodiments, preferably r1 = 20 and r2 = 50. In certain embodiments, preferably r1 = 20, and r2 = 40. In certain embodiments, preferably r1 = 20, and r2 = 30. The ratio r(s / a) can be determined by ICP-MS (inductively coupled plasma mass spectrometry) or XRF (X-ray fluorescence).

[0048] In certain embodiments, the MEL framework type zeolite material of the present disclosure may have a value that can range from a1 to a2m 2The BET total specific surface area A(st) varying with / g, where a1 and a2 can independently be, for example, 300, 320, 340, 350, 360, 380, 400, 420, 440, 450, 460, 480, 500, 520, 540, 550, 560, 580, 600, provided that a1 < a2. In certain embodiments, preferably a1 = 400 and a2 = 500. In certain embodiments, preferably a1 = 400 and a2 = 475. A(st) can be measured by the BET method (Brunauer - Emmet - Teller method, nitrogen adsorption method). The high total surface area A(st) of the zeolite material of the present disclosure is another reason for its high catalytic activity when used as a catalyst (such as a catalyst for the conversion of aromatic hydrocarbons). The BET method can produce the total specific surface area of the measured material, including the micropore specific surface area component and the mesopore specific surface area component. In the present disclosure, the mesopore specific area can be referred to as the mesopore area, mesoporous area, or external area. In the present disclosure, the total specific surface area can be referred to as the total surface area or total area.

[0049] In certain embodiments, the MEL framework type zeolite material of the present disclosure can have a mesopore area A(mp) that is ≥15% (such as ≥16%, ≥18%, ≥20%, ≥22%, ≥24%, ≥25%) of the above - mentioned total surface area A(st). In certain embodiments, preferably A(mp) ≥ 20% × A(st). In certain embodiments, preferably A(mp) ≤ 40% × A(st). In certain embodiments, preferably A(mp) ≤ 30% × A(st). The high mesopore area A(mp) of the zeolite material of the present disclosure is another reason for its high catalytic activity when used as a catalyst (such as a catalyst for the conversion of aromatic hydrocarbons). Without wishing to be bound by a particular theory, it is believed that the catalytic sites present on the mesopore area of the zeolite material of the present disclosure are more numerous due to the high mesopore area, and they tend to contribute more to the catalytic activity than the catalytic sites located in the deep channels inside the zeolite material. The time required for reactant molecules to reach the catalytic sites on the mesopore surface and for product molecules to leave them is shorter. In contrast, it will take a significantly longer time for reactant molecules to diffuse into the deep channels and for product molecules to diffuse out of them.

[0050] In certain embodiments, the MEL framework type zeolite material of the present disclosure may have a hexane adsorption value of v(hs), which may be from v1 to v2 mg / g, where v1 and v2 may independently be, for example, 90, 92, 94, 95, 96, 98, 100, 102, 104, 105, 106, 108, 110, provided that v1 < v2. The hexane adsorption value can be determined by TGA (thermogravimetric analysis) typical in the industry.

[0051] In certain embodiments, the MEL framework type zeolite material of the present disclosure may have an α value that can vary from a1 to a2, where a1 and a2 may independently be, for example, 500, 600, 700, 800, 900, 1000, 1200, 1400, 1500, 1600, 1800, 2000, 2200, 2400, 2500, 2600, 2800, 3000, provided that a1 < a2. The α value can be determined by the methods described in U.S. Patent No. 3,354,078 and Journal of Catalysis, Vol. 4, p. 527 (1965); Vol. 6, p. 278 (1966) and Vol. 61, p. 395 (1980).

[0052] II. Method for Preparing a Novel Class of MEL Zeolite Materials According to the Second Aspect of the Present Disclosure The synthesis of molecular sieve materials generally involves preparing a synthesis mixture that contains sources of all the elements present in the molecular sieve and usually has a source of hydroxide ions for adjusting the pH value. In many cases, there is also a structure directing agent (also referred to as a templating agent or template). A structure directing agent is a compound that is thought to promote the formation of the molecular sieve and is thought to act as a template around which certain molecular sieve structures can form and thus promote the formation of the desired molecular sieve. Various compounds have been used as structure directing agents, including various types of quaternary ammonium cations.

[0053] The synthesis of molecular sieves is a complex process. Many variables need to be controlled in order to optimize the synthesis in terms of the purity, yield, and quality of the prepared molecular sieve. A particularly important variable is the choice of the synthesis template (structure directing agent), which generally determines which framework type is obtained from the synthesis. Quaternary ammonium ions are commonly used as structure directing agents in the preparation of zeolite catalysts.

[0054] "As-synthesised" molecular sieves will contain structure directing agents in their pores, and typically undergo a calcination step to burn out the structure directing agents and release the pores. For many catalytic applications, it is desirable to convert the molecular sieve to the hydrogen form (H-form). This can be achieved by first removing the structure directing agent by calcination in air or nitrogen, then ion exchange to replace the alkali metal cations (usually sodium cations) with ammonium cations, and then subjecting the molecular sieve to a final calcination to convert the ammonium form to the H-form. The H-form can then be subjected to various "post-treatments", such as steaming and / or acid treatment, to tailor the surface properties of the crystals. The product of such treatment is often referred to as "post-treated".

[0055] The present inventors have found that it is possible to prepare MEL framework-type zeolites having very small crystal sizes and having high mesopore surface areas, in particular by selecting the synthesis mixture composition.

[0056] The structure directing agent ("SDA") is selected from TBA, alkyl diamines containing 7-12 carbon atoms, and mixtures and combinations thereof. As used herein, "TBA" refers to a tetrabutylammonium cation. Examples of alkyl diamines containing 7-12 carbon atoms include, but are not limited to, heptane-1,7-diamine, octane-1,8-diamine, nonane-1,9-diamine, decane-1,10-diamine, and undecane-1,11-diamine. Preferably, the structure directing agent is TBA. TBA may be included in the synthesis mixture as a halide, hydroxide, any mixture thereof, or the like. Chloride, fluoride, bromide, iodide, or mixtures thereof of TBA may be used. The preferred salt of TBA is TBA bromide, abbreviated herein as TBABr. Preferably, the molar ratio of SDA:Si is 0.005-0.20, and more preferably 0.01-0.10, particularly 0.02-0.05.

[0057] The molar ratio Si:Al of the MEL framework type zeolite of the present disclosure 2 (also called silicon dioxide and aluminum oxide or SiO 2 / Al 2 O 3 The Si:Al ratio of the post-treated MEL framework type zeolite of the present disclosure is preferably greater than 10, and may be, for example, in the range of 10-60, preferably 15-50, preferably 15-40, preferably 15-30, for example 20-30, for example 22-28. 2 The ratio is preferably 20-300, and more preferably 20-100.

[0058] Suitable silicon (Si) sources include silica, colloidal suspensions of silica, precipitated silica, alkali metal silicates such as potassium silicate and sodium silicate, tetraalkyl orthosilicates, and fumed silica such as Aerosil TMCabosil TM Preferably, the Si source is precipitated silica, such as Ultrasil TM (available from Evonik Degussa) or Hisil TM (Available from PPG Industries).

[0059] Suitable aluminum (Al) sources include aluminum sulfate, aluminum nitrate, aluminum hydroxide, hydrated aluminum oxides such as boehmite, gibbsite and / or pseudoboehmite, sodium aluminate, and mixtures thereof. Other aluminum sources include, but are not limited to, other water-soluble aluminum salts, or aluminum alkoxides, such as aluminum isopropoxide, or aluminum metal, such as aluminum in the form of fragments. Preferably, the aluminum source is sodium aluminate, such as a sodium aluminate aqueous solution having a concentration of 40-45%, or aluminum sulfate, such as an aluminum sulfate solution having a concentration of 45-50%.

[0060] As an alternative or in addition to the previously mentioned Si and Al sources, aluminosilicates may also be used as a source of both Si and Al.

[0061] Preferably, the Si:Al in the synthesis mixture 2 The ratio is 15-70, and more preferably 15-50, and more preferably 15-40, such as 20-30.

[0062] The synthetic mixture also contains an alkali metal cation M + Source. Alkali metal cation M + Preferably, the sodium source is selected from sodium, potassium and a mixture of sodium and potassium cations. Sodium cations are preferred. Suitable sodium sources may be, for example, sodium salts such as NaCl, NaBr or NaNO 3 , sodium hydroxide or sodium aluminate, preferably sodium hydroxide or sodium aluminate. Suitable potassium sources may be, for example, potassium hydroxide or potassium halides such as KCl or KBr, or potassium nitrate. Preferably, M in the synthesis mixture + The Si:Si ratio is from 0.1 to 0.5, and more preferably from 0.2 to 0.4.

[0063] The synthesis mixture also contains a source of hydroxide ions, for example an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide. The hydroxide may also be present as a counter ion of the structure directing agent or by using aluminum hydroxide as an Al source. Preferably, OH - :Si ranges from greater than 0.05 and may be, for example, in the range of 0.05 to 0.5. Optionally, OH - :Si ratio is less than 0.3.

[0064] The synthesis mixture optionally comprises seed crystals. The seed crystals can be any suitable zeolite seed crystals, such as ZSM-5 or ZSM-11 seed crystals. Preferably, the seed crystals are mesoporous ZSM-11 crystals. Preferably, the seed crystals have a crystallite size of ≤100 nanometers. Such seed crystals of small crystallite size are particularly advantageous for preparing ZSM-11 crystals with small crystallite size of the present disclosure. The seed crystals can, for example, account for about 0 to 20 wt %, particularly about 0 to 10 wt %, preferably about 0.01 to 10 wt %, for example, about 0.1 wt % to about 5.0 wt % of the synthesis mixture. In a preferred embodiment, the synthesis mixture comprises seed crystals.

[0065] The present inventors have found that having a higher solids content in the synthesis mixture is beneficial for the synthesis of small crystal MEL framework type zeolites. 2 The O:Si molar ratio is not greater than 20, for example, in the range of 5 to 20, preferably 5 to 15, especially 10 to 15.

[0066] The synthesis mixture may, for example, have a composition expressed in molar ratios as shown in Table A below:

[0067] Table A

[0068] Molar Ratio Best More preferred Especially preferred <![CDATA[Si:Al 2 ]]> 15-70 15-40 20-30 <![CDATA[OH - :Yes]]> 0.05-0.5 0.05-0.3 0.05-0.2 <![CDATA[M + :Yes]]> 0.10-0.50 0.10-0.40 0.20-0.40 SDA:Si 0.005-0.20 0.01-0.1 0.02-0.08 <![CDATA[H 2 Oh:Yes]]> 5-20 5-15 10-15

[0069] Crystallization can be carried out under static or stirred conditions in a suitable reaction vessel, such as a polypropylene tank or Lined or stainless steel autoclave. Suitable crystallization conditions include temperatures of about 100°C to about 200°C, such as about 135°C to about 160°C. Preferably, the temperature is less than 150°C. The synthesis mixture can be kept at an elevated temperature for a time sufficient for crystallization to occur at the temperature used, such as about 1 day to about 100 days, optionally 1 to 50 days, such as about 2 days to about 40 days. In some cases, the synthesis mixture can be kept at a first temperature for a first period of 1 hour to 10 days, and then raised to a second higher temperature for a period of 1 hour to 40 days. After the crystallization step, the synthesized crystals are separated from the liquid, washed, and then recovered.

[0070] Because the as-synthesized MEL framework-type zeolites of the present disclosure contain a structure directing agent within their pore structure, the product is typically activated prior to use in a manner such that the organic portion of the structure directing agent, ie, TBA, is at least partially removed from the zeolite.

[0071] The calcined MEL framework type zeolite of the present disclosure is optionally prepared by calcining the MEL framework type zeolite of the present disclosure to remove the structure directing agent. The MEL framework type zeolite may also undergo an ion exchange step to replace the alkali metal or alkaline earth metal ions present in the product as it is when synthesized with other cations. Preferred alternative cations include metal ions, hydrogen ions, hydrogen precursors such as ammonium ions and mixtures thereof, and more preferably hydrogen ions or hydrogen precursors. For example, the MEL framework type zeolite of the present disclosure may undergo an ion exchange step to replace the alkali metal or alkaline earth metal ions with ammonium cations, and then calcined to convert the zeolite in the ammonium form into the zeolite in the hydrogen form. In one embodiment, first the MEL framework type zeolite of the present disclosure undergoes a calcination step, sometimes referred to as "pre-calcination", to remove the structure directing agent from the pores of the MEL framework type zeolite, then undergoes an ion exchange treatment, and then undergoes other calcination steps.

[0072] The ion exchange step may include, for example, contacting the MEL framework type zeolite with an ion exchange aqueous solution. This contact may occur, for example, 1 to 5 times. The contact with the ion exchange solution is optionally at ambient temperature, or alternatively may be at an elevated temperature. For example, the zeolite of the present disclosure may be ion exchanged by contacting with an aqueous ammonium nitrate solution at room temperature, followed by drying and calcining.

[0073] Suitable calcining conditions include heating at a temperature of at least about 300° C., preferably at least about 400° C., for at least 1 minute, typically for a period of no longer than 20 hours, such as 1 hour to 12 hours. Although pressures below atmospheric pressure can be used for heat treatment, atmospheric pressure is desirable for convenience. For example, heat treatment can be carried out at a temperature of 400 to 600° C., such as 500 to 550° C., in the presence of an oxygen-containing gas.

[0074] The calcined MEL framework-type zeolites of the present disclosure generally have a chemical composition having the following molar relationship: nSiO 2 :Al 2 O 3 , wherein n is at least 10, for example 10 to 60, more particularly 15 to 40, and more preferably 20 to 40, and more preferably 20 to 30.

[0075] The calcined MEL framework-type zeolite of the present disclosure can be used as a catalyst or adsorbent as is without further treatment, or it can be post-treated, such as steaming and / or acid washing.

[0076] Optionally, the calcined zeolite of the present disclosure is subjected to steam treatment at a temperature of at least 200°C, preferably at least 350°C, and more preferably at least 400°C, in some cases at least 500°C, for a period of 1 to 20 hours, preferably 2 to 10 hours. Optionally, the steamed zeolite is then treated with an aqueous solution of an acid, preferably an organic acid, such as a carboxylic acid. Oxalic acid is a preferred acid. Optionally, the steamed zeolite is treated with an aqueous solution of an acid at a temperature of at least 50°C, preferably at least 60°C, for a period of at least 1 hour, preferably at least 4 hours, for example 5 to 20 hours.

[0077] Preferably, the chemical composition of the post-treated MEL framework type zeolite has the following molar relationship: nSiO 2 :Al 2 O 3 , wherein n is at least 20, and more preferably at least 50, and in some cases at least 100.

[0078] III. Catalyst composition of the third aspect of the present disclosure comprising the novel MEL zeolite material of the first aspect

[0079] The MEL framework type zeolite of the present disclosure can be used directly as a catalyst, or can be compounded with one or more other components such as a binder and / or a second zeolite material. The MEL framework type zeolite can be used as an adsorbent or catalyst to catalyze a variety of organic compound conversion processes, including many organic compound conversion processes of current commercial / industrial importance. The conversion of hydrocarbon feeds can be carried out in any convenient mode, for example, in a fluidized bed, moving bed or fixed bed reactor, depending on the desired process type.

[0080] The third aspect of the present disclosure relates to a catalyst composition comprising the MEL framework type zeolite of the first aspect of the present disclosure described above. The catalyst composition may be substantially free of any other components except the MEL framework type zeolite. In this case, the MEL framework type zeolite is a self-supporting catalyst composition.

[0081] When used as an adsorbent or catalyst in a catalyst composition in an organic compound conversion process, the MEL framework-type zeolite of the present disclosure should preferably be at least partially dehydrated. This can be carried out by heating to a temperature of about 100° C. to about 500° C., such as about 200° C. to about 370° C., for 30 minutes to 48 hours in an atmosphere such as air, nitrogen, etc., at atmospheric pressure, subatmospheric pressure, or superatmospheric pressure. Dehydration can also be carried out at room temperature simply by placing the MEL framework-type zeolite in a vacuum, but longer times are required to obtain a sufficient amount of dehydration.

[0082] The MEL framework type zeolite of the present disclosure can be formulated into a catalyst composition by combining with other materials such as hydrogenation components, binders and / or matrix materials, which provide additional hardness or catalytic activity for the finished catalyst. These other materials can be inert or catalytically active materials. In particular, the MEL framework type zeolite of the present disclosure can be combined with a second zeolite, such as a zeolite having a 10-membered or 12-membered ring structure in its crystallites. Non-limiting examples of such a second zeolite include: MWW framework type zeolites, such as MCM-22, MCM-49 and MCM-56; MFI framework type zeolites such as ZSM-5; MOR framework zeolites, such as mordenite, etc.; and mixtures and combinations thereof. The second zeolite may preferably have a constraint index of 0.5 to 15. When a second zeolite is included in the catalyst composition, it is preferred that the concentration of the MEL framework type zeolite in the catalyst composition is ≥50wt%, for example ≥60wt%, ≥70wt%, ≥80wt%, ≥90wt%, ≥95wt%, based on the total weight of the MEL framework type zeolite and the second zeolite.

[0083] When the hydrogenation-dehydrogenation function is to be brought into play, the MEL framework type zeolite described herein can be closely combined with hydrogenation components such as tungsten, vanadium, molybdenum, rhenium, nickel, cobalt, chromium, manganese or noble metals such as platinum or palladium. Such a component can be incorporated into the composition by cocrystallization, exchanged into the composition to reach the degree of IIIA group elements (such as aluminum) in the structure, impregnated therein or closely physically mixed with it. Such a component can be impregnated in or on the MEL framework type zeolite, for example, in the case of platinum, by treating the MEL framework type zeolite with a solution containing ions of platinum metal. Therefore, suitable platinum compounds for this reason include chloroplatinic acid, platinum dichloride and various compounds containing platinum amine complexes. It is also possible to use a combination of metals and their introduction methods.

[0084] As in the case of many catalysts, it may be desirable to combine the MEL framework type zeolite of the present disclosure with other materials that tolerate the temperature and other conditions used in the organic conversion process. Such materials include active and inactive materials and synthetic or naturally occurring zeolites, as well as inorganic materials, such as clays, silica and / or metal oxides, such as alumina. The latter can be naturally occurring or in the form of a gelatinous precipitate or gel comprising a mixture of silica and metal oxides. The use of active materials combined with the MEL framework type zeolite, i.e., in combination with it or present during the synthesis of the MEL framework type zeolite, tends to change the conversion rate and / or selectivity of the catalyst in certain organic conversion processes. Inactive materials suitably act as diluents to control the amount of conversion in a given method so that the product can be obtained in an economical and orderly manner without the need to adopt other means to control the reaction rate. These materials can be incorporated into naturally occurring clays, such as montmorillonite, bentonite, subbentonite and kaolin, such as kaolin commonly known as Dixie, McNamee, Georgia and Florida clays, or other clays whose main mineral components are halloysite, kaolinite, nacrite or wormwood, to improve the crushing strength of the catalyst under commercial operating conditions. Such clays can be used in their original state when originally mined or after calcination, acid treatment or chemical modification. These binder materials tolerate temperature and other conditions, such as mechanical wear and tear that occurs during various hydrocarbon conversion processes. Therefore, the MEL framework type zeolite of the present disclosure or manufactured by the method of the present disclosure can be used in the form of an extrudate with a binder. They are usually combined by forming pellets, spheres or extrudates. The extrudate is usually formed as follows: the molecular sieve is optionally extruded in the presence of a binder, and the extrudate obtained is dried and calcined.

[0085] The use of materials combined with the MEL framework type zeolite of the present disclosure or manufactured by the method of the present disclosure (i.e., in combination with it or present during zeolite synthesis) tends to change the conversion rate and / or selectivity of the catalyst in certain organic conversion methods. Inactive materials suitably act as diluents to control the amount of conversion in a given method so that the product can be obtained in an economical and orderly manner without the need to adopt other means of controlling the reaction rate. These materials can be incorporated into naturally occurring clays, such as bentonite and kaolin, to improve the crushing strength of the catalyst under commercial operating conditions.

[0086] In addition to the aforementioned materials, the MEL framework-type zeolite of the present disclosure can be composited with porous matrix materials such as silica-alumina, silica-magnesia, silica-zirconia, silica-thoria, silica-beryllia, silica-titania, and ternary compositions such as silica-alumina-thoria, silica-alumina-zirconia, silica-alumina-magnesia, and silica-magnesia-zirconia.

[0087] The relative proportions of the MEL framework type zeolite and the inorganic oxide matrix can vary widely, with the MEL framework type zeolite content ranging from about 1 to about 100 weight percent, more typically, especially when the composite is prepared in the form of beads or extrudates, from about 50 to about 80 weight percent of the composite.

[0088] The preferred binder in the catalyst composition is a high surface area binder, for example, a binder with a specific surface area ≥ 200 m 2 / g, even ≥250m 2 / g high surface area alumina. Specific surface area ≤150m 2 Low surface area alumina of 1000 g / g may also work. Silica has been shown to be a useful binder in catalyst compositions.

[0089] When preparing the catalyst composition, the MEL framework type zeolite of the first aspect of the present disclosure in hydrogen form, alkali form or other form as it is when synthesized or calcined can be mixed with other materials such as a binder, a second zeolite and / or a hydrogenation metal and other components such as water. The mixture can be formed into a desired shape by, for example, extrusion, molding, etc. The catalyst composition so formed can be optionally dried and calcined in nitrogen and / or air to obtain the catalyst composition. The catalyst composition can be further ion exchanged with an ammonium salt solution, then dried and calcined to obtain the catalyst composition in hydrogen form.

[0090] The catalyst composition of the second aspect of the present disclosure may take any shape: cylinder, solid sphere, trilobate, quadrilobate, eggshell sphere, etc. The catalyst composition may be ground into a powder and used as is.

[0091] In the method of preparing the catalyst composition of the second aspect of the present disclosure from the MEL framework-type zeolite of the first aspect of the present disclosure, some primary crystallites in the MEL framework-type zeolite material may further agglomerate to form additional agglomerates or make the size of existing agglomerates larger.

[0092] IV. Methods for converting aromatic hydrocarbons using MEL zeolite materials according to the fourth and fifth aspects of the present disclosure

[0093] Certain MEL framework type zeolites are known. An example of a MEL framework type zeolite is the ZSM-11 zeolite described, for example, in U.S. Patent Nos. 3,709,979; 3,804,746; 4,108,881; 4,941,963; 5,213,786; and 6,277,355. ZSM-11 is reportedly used for catalytic dewaxing in the production of hydrocarbon fuel products. See, for example, Canadian Patent No. CA1281677C.

[0094] The use of MEL framework-type zeolites in a process for converting aromatic hydrocarbons such as C8 aromatic hydrocarbons is novel in itself. Therefore, a fourth aspect of the present disclosure relates to a process for converting a feed comprising C8 aromatic hydrocarbons, the process comprising: (I) feeding the aromatic hydrocarbon feed into a conversion reactor; and (II) contacting at least a portion of the C8 aromatic hydrocarbons in a liquid phase with a conversion catalyst composition comprising a MEL framework-type zeolite under conversion conditions to isomerize at least a portion of the C8 aromatic hydrocarbons to produce a conversion product effluent.

[0095] A high purity p-xylene product is generally produced by separating p-xylene from a p-xylene-rich aromatic hydrocarbon mixture comprising p-xylene, o-xylene, m-xylene, and optionally, EB in a p-xylene separation / recovery system. The p-xylene recovery system may include, for example, a crystallizer and / or an adsorption chromatography separation system known in the prior art. The p-xylene-poor stream produced by the p-xylene recovery system (the "filtrate" from the crystallizer when separating p-xylene crystals, or the "raffinate" from the adsorption chromatography separation system, collectively referred to as "raffinate" in the present disclosure) is rich in m-xylene and o-xylene, and contains p-xylene at a concentration generally lower than its concentration in an equilibrium mixture consisting of m-xylene, o-xylene, and p-xylene. In order to increase the yield of p-xylene, the raffinate stream may be fed to an isomerization unit, wherein the xylene undergoes an isomerization reaction in a contact isomerization catalyst system to produce an isomerization effluent rich in p-xylene compared to the raffinate. After optional separation and removal of light hydrocarbons that may be produced in the isomerization unit, at least a portion of the isomerization effluent may be recycled to the para-xylene recovery system, forming a "xylene loop."

[0096] Xylene isomerization can be carried out under conditions where the C8 aromatics are substantially in the vapor phase in the presence of an isomerization catalyst (vapor phase isomerization, or "VPI").

[0097] A new generation of technology has been developed to allow the isomerization of xylenes at significantly lower temperatures in the presence of an isomerization catalyst, with the C8 aromatics being substantially in the liquid phase (liquid phase isomerization, or "LPI"). The use of LPI relative to conventional VPI can reduce the number of phase changes (liquid to vapor / vapor to liquid) required to process C8 aromatic feeds. This provides a sustainability advantage to the process in the form of significant energy savings. For any paraxylene production unit, it would be highly advantageous to deploy an LPI unit in addition to or in place of a VPI unit. For existing paraxylene production facilities that lack LPI, it would be highly advantageous to add an LPI unit to supplement the VPI unit or to replace the VPI unit.

[0098] Exemplary LPI processes and catalyst systems useful therefor are described in U.S. Patent Application Publication Nos. 2011 / 0263918 and 2011 / 0319688, 2017 / 0297977, 2016 / 0257631, and U.S. Patent No. 9,890,094, the contents of which are incorporated herein by reference in their entirety. In the LPI processes described in these references, MFI framework type zeolites (e.g., ZSM-5) are typically used as catalysts.

[0099] Surprisingly, it has been found that ZSM-11 zeolite can be used for LPI of C8 aromatic hydrocarbons, and that the catalyst performance is significantly improved at WHSV of conventional LPI processes, for example at 2.5 and 5 hours, compared to processes using ZSM-5 zeolite as a catalyst. -1 This results in significantly lower xylene losses.

[0100] It has been found even more surprisingly that by using a material having a small crystallite size and / or a low SiO 2 / Al 2 O 3 Compared with the novel ZSM-11 zeolite of the present disclosure, the LPI process can achieve very high para-xylene selectivity over a wide range of WHSVs, such as 2.5 and 5.0 hours. -1 , and at high WHSV>5 hours -1 , such as ≥ 10 hours -1 , or ≥ 15 hours -1 and up to 20 hours -1 Such high throughput LPI processes, which are not normally feasible using MFI framework type zeolites such as ZSM-5 (and now made possible by the novel MEL framework type zeolites of the present disclosure), may be particularly attractive.

[0101] Any MEL framework type zeolite may be included in the conversion catalyst composition. Preferably, the MEL framework type zeolite is at least partially in hydrogen form. Preferably, the MEL framework zeolite is calcined.

[0102] The MEL framework zeolite in the conversion catalyst composition included in the aromatic hydrocarbon conversion process of the present disclosure may advantageously have an SiO 2 / Al 2 O 3 molar ratio of 10 - 60, preferably 15 - 50, preferably 15 - 40, preferably 20 - 40, such as 20 - 30. The lower this ratio, the higher the activity of the zeolite in catalyzing the conversion of aromatic hydrocarbons tends to be.

[0103] The MEL framework zeolite included in the conversion catalyst composition may advantageously comprise a plurality of small microcrystals, such as those having a microcrystal size of ≤200 nm, preferably ≤150 nm, preferably ≤100 nm, preferably ≤80 nm, preferably ≤70 nm, preferably ≤60 nm, preferably ≤50 nm, such as ≤30 nm as determined by TEM imaging analysis. At such a small microcrystal size, the zeolite is particularly effective and efficient in catalyzing the conversion of aromatic hydrocarbons, especially the isomerization of xylene.

[0104] The microcrystals forming the MEL framework zeolite included in the conversion catalyst composition may comprise, based on the total number of microcrystals, ≥75%, such as ≥80%, ≥85%, ≥90%, ≥95%, up to 98% of the microcrystals having a microcrystal size of ≤200 nm, preferably ≤150 nm, preferably ≤100 nm, preferably ≤80 nm, preferably ≤70 nm, preferably ≤60 nm, preferably ≤50 nm, preferably ≤50 nm, such as ≤30 nm as determined by TEM imaging analysis.

[0105] The microcrystals forming the MEL framework type zeolite included in the conversion catalyst composition may form many aggregates with irregular shapes.

[0106] The MEL framework zeolite included in the conversion catalyst composition may advantageously have a BET total surface area A(st) that can vary from a1 to a2 m 2 / g, where a1 and a2 can independently be, for example, 300, 320, 340, 350, 360, 380, 400, 420, 440, 450, 460, 480, 500, 520, 540, 550, 560, 580, 600, as long as a1 < a2. In certain embodiments, preferably a1 = 400 and a2 = 500. In certain embodiments, preferably a1 = 400 and a2 = 475.

[0107] The MEL framework zeolite contained in the conversion catalyst composition can advantageously have a mesopore surface area A(mp) of ≥15% (e.g., ≥16%, ≥18%, ≥20%, ≥22%, ≥24%, ≥25%) of the above-mentioned total surface area A(st). In certain embodiments, it is preferred that A(mp) ≥20%×A(st). In certain embodiments, it is preferred that A(mp) ≤40%×A(st). In certain embodiments, it is preferred that A(mp) ≤30%×A(st). The high mesopore area A(mp) of the zeolite material of the present disclosure is another reason why it exhibits high catalytic activity when used as a catalyst (e.g., a catalyst for converting aromatic hydrocarbons).

[0108] In addition to the MEL framework type zeolite, the conversion catalyst composition may also include a binder such as alumina, silica, zirconia, zircon, chromium oxide, kaolin and other refractory materials, and mixtures and combinations thereof. A binder having a high surface area is preferred, such as high surface area silica, high surface area silica.

[0109] In addition to the MEL framework type zeolite, the conversion catalyst composition can also include a second zeolite, such as a zeolite of the MFI framework type (e.g., ZSM-5), a zeolite of the MWW framework type (e.g., MCM-22, MCM-49, etc.), and mixtures and combinations thereof. When the second zeolite is included, it is preferred that the MEL framework type zeolite is included in a concentration of ≥50wt%, such as ≥60wt%, ≥70wt%, ≥80wt%, ≥90wt%, or even ≥95wt%, based on the total weight of the MEL framework type zeolite and the second zeolite. This second zeolite preferably has a 10-membered or 12-membered ring and its microcrystalline structure. This second zeolite preferably has a constraint index of 0.5-15, preferably 1-10.

[0110] Particularly advantageous MEL framework zeolites that may be included in the conversion catalyst composition used in the aromatic hydrocarbon conversion process of the present disclosure are those of the first aspect of the present disclosure, as described in detail above.

[0111] When contacting C8 aromatic hydrocarbons, especially xylene molecules, the xylene molecules can undergo isomerization reactions. Typically, the aromatic hydrocarbon feed comprises para-xylene, ortho-xylene, meta-xylene and EB. The aromatic hydrocarbon feed can be part of the raffinate from a para-xylene separation / recovery system.

[0112] The aromatic feed may be derived from, for example, the effluent from a C8 aromatic hydrocarbon distillation column, a p-xylene-depleted raffinate stream produced by a p-xylene separation / recovery system comprising an adsorption chromatography system, or a p-xylene-depleted filtrate stream produced by a p-xylene separation / recovery system comprising a p-xylene crystallizer, or a mixture thereof. In the present disclosure, the raffinate stream and the filtrate stream are hereinafter collectively referred to as the raffinate stream.

[0113] In certain embodiments, the aromatic hydrocarbon feed may contain various concentrations of p - xylene C(pX) of c1 to c2 wt%, based on the total weight of C8 aromatic compounds present in the aromatic hydrocarbon feed, where c1 and c2 can independently be, for example, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, provided that c1 < c2. Generally, C(pX) is lower than the p - xylene concentration in an equilibrium mixture composed of p - xylene, m - xylene, and o - xylene at the same temperature. Preferably, C(pX) ≤ 15. More preferably, C(pX) ≤ 10. Even more preferably, C(pX) ≤ 8.

[0114] In certain embodiments, the aromatic hydrocarbon feed may contain various concentrations of m - xylene C(mX) of m1 to m2 wt%, based on the total weight of C8 aromatic compounds present in the aromatic hydrocarbon feed, where m1 and m2 can independently be, for example, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, or 80, provided that m1 < m2. C(mX) can be significantly higher than the m - xylene concentration in an equilibrium mixture composed of p - xylene, m - xylene, and o - xylene at the same temperature, especially if the aromatic hydrocarbon feed consists essentially only of xylenes and is substantially free of EB.

[0115] In certain embodiments, the aromatic hydrocarbon feed may contain various concentrations of o - xylene C(oX) of n1 - n2 wt%, based on the total weight of C8 aromatic compounds present in the aromatic hydrocarbon feed, where n1 and n2 can independently be, for example, 10, 15, 20, 25, 30, 35, 40, 45, 50, provided that n1 < n2. C(oX) can be significantly higher than the o - xylene concentration in an equilibrium mixture composed of p - xylene, m - xylene, and o - xylene at the same temperature, especially if the aromatic hydrocarbon feed consists essentially only of xylenes and is substantially free of EB.

[0116] Among all the xylenes present in the aromatic hydrocarbon feed, m - xylene and o - xylene can be present in any ratio. Thus, the ratio of m - xylene to o - xylene can be from r1 to r2, where r1 and r2 can independently be, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, provided that r1 < r2.

[0117] In certain embodiments, the aromatic hydrocarbon feedstock supplied to the conversion reactor may contain a total xylene concentration of C(aX) wt%, based on the total weight of the aromatic hydrocarbon feedstock, where C(aX) wt% is from c3 to c4 wt%, and c3 and c4 may independently be, for example, 50, 55, 60, 65, 70, 75, 80, 85, 90, 91, 92, 93, 94, 95, 96, 97, 98, or 99, provided that c3 < c4. The aromatic hydrocarbon feedstock may consist essentially of xylene and EB.

[0118] In certain embodiments, the aromatic hydrocarbon feedstock may contain a C(EB) wt% concentration of EB from c5 to c6 wt%, based on the total weight of the aromatic hydrocarbon feedstock, where c5 and c6 may independently be, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, 14, 15, 16, 18, 20, 22, 24, 25, 26, 28, 30, provided that c5 < c6. Preferably, 2 ≤ C(EB) ≤ 25. More preferably, 3 ≤ C(EB) ≤ 20. Even more preferably, 5 ≤ C(EB) ≤ 15.

[0119] In certain embodiments, the aromatic hydrocarbon feedstock contains C8 aromatic hydrocarbons (i.e., xylene and EB) at a total concentration of, for example, ≥90, or ≥92, or ≥94, or ≥95, or ≥96, or ≥98, or even ≥99 wt%, based on the total weight of the aromatic hydrocarbon feedstock.

[0120] In certain embodiments, the aromatic hydrocarbon feedstock may contain a C(C9+A) wt% concentration of C9+ aromatic hydrocarbons, based on the total weight of the aromatic hydrocarbon feedstock, where C(C9+A) wt% is from c7 to c8 wt%, and c7 and c8 may independently be, for example, 1, 20, 40, 50, 60, 80, 100, 200, 400, 500, 600, 800, 1000, provided that c7 < c8.

[0121] Depending on its source (e.g., xylene distillation column, para-xylene crystallizer, or adsorption chromatography separation system), the aromatic hydrocarbon feedstock may contain various amounts of toluene, but typically not more than 1 wt%, based on the total weight of the aromatic hydrocarbon feedstock.

[0122] Depending on its source, the aromatic hydrocarbon feedstock may contain various amounts of C7-aromatic hydrocarbons (total of toluene and benzene), e.g., c9 to c10 wppm by weight, based on the total weight of the aromatic hydrocarbon feedstock, where c9 and c10 may independently be, for example, 10, 20, 40, 50, 60, 80, 100, 200, 400, 500, 600, 800, 1000, 2000, 4000, 5000, 6000, 8000, 10000, 20000, provided that c9 < c10.

[0123] Exemplary conversion conditions in the aromatic hydrocarbon conversion process of the present disclosure may include a temperature of t1 to t2 °C, where t1 and t2 may independently be, for example, 100, 120, 140, 150, 160, 180, 200, 220, 240, 250, 260, 280, 300, 320, 340, 350, provided that t1 < t2. Preferably, t1 = 150 and t2 = 300. Preferably, t1 = 180 and t2 = 300. Preferably, t1 = 200 and t2 = 280. Preferably, t1 = 220 and t2 = 260. Preferably, t1 = 240 and t2 = 260. Compared with conventional VPI processes that typically operate at significantly higher temperatures, the low operating temperature of this process can result in significant energy savings.

[0124] Exemplary conversion conditions in the aromatic hydrocarbon conversion process of the present disclosure may include a WHSV of w1 to w2 hours -1 based on the flow rate of the aromatic hydrocarbon feed and the weight of the conversion catalyst composition, where w1 and w2 may independently be, for example, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.0, 9.5, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, provided that w1 < w2. Preferably, w1 = 1.0 and w2 = 20. Preferably, w1 = 2.0 and w2 = 20. Preferably, w1 = 5.0 and w2 = 20. Preferably, w1 = 8.0 and w2 = 10. Preferably, w1 = 5.0 and w2 = 15. Preferably, w1 = 10 and w2 = 15. Such high-throughput processes where w1 > 5.0, such as w1 ≥ 8.0, w1 ≥ 10, w1 ≥ 15, can be particularly advantageous. As described above and demonstrated in the following examples, by using certain MEL framework type zeolites of the first aspect of the present disclosure, high para-xylene selectivity can be achieved at such high WHSV that is not feasible in conventional processes using ZSM-5 based catalysts.

[0125] Exemplary conversion conditions in the aromatic hydrocarbon conversion process of the present disclosure generally include the internal pressure in the conversion reactor, which is sufficient to keep most of the C8 aromatic hydrocarbons in the aromatic hydrocarbon feed, for example, ≥ 80 mol%, for example, ≥ 85 mol%, ≥ 90 mol%, ≥ 95 mol%, ≥ 98 mol% or even substantially all, in the liquid phase at a given temperature in the conversion reactor. For example, for an LPI reaction temperature of 240 °C, the pressure is generally ≥ 1830 kPa.

[0126] Exemplary conversion conditions in the aromatic hydrocarbon conversion process of the present disclosure may include feeding molecular hydrogen into the conversion reactor. Any suitable amount of molecular hydrogen can be supplied to the conversion reactor. An exemplary amount of molecular hydrogen supplied to the conversion reactor can be h1 to h2 wppm, based on the total weight of the aromatic hydrocarbon feed, where h1 and h2 can be, for example, 1, 2, 4, 5, 6, 8, 10, 20, 40, 50, 60, 80, 100, 200, 400, 500, 600, 800, or 1000, provided that h1 < h2. Preferably h1 = 4 and h2 = 250. When molecular hydrogen is supplied to the conversion reactor, it is highly desirable that the pressure in the conversion reactor be maintained sufficient to dissolve most, e.g., ≥80%, ≥85%, ≥90%, ≥95%, ≥98%, or even substantially all of the molecular hydrogen in the aromatic hydrocarbon feed, such that the conversion reaction in the conversion reactor is substantially in the liquid phase. While not wishing to be bound by a particular theory, it is believed that co-feeding a certain amount of molecular hydrogen into the conversion reactor can inhibit coke formation on the conversion catalyst composition, thereby extending the life of the conversion catalyst composition.

[0127] It has surprisingly been found that in the LPI process, in the absence of co-feeding hydrogen into the LPI reactor, the conversion catalyst composition comprising a zeolite of the MEL framework type, in particular the zeolite of the MEL framework type of the first aspect of the present disclosure, exhibits a much lower deactivation rate compared to a catalyst composition based on an MFI zeolite, such as a catalyst composition based on ZSM-5. While it is desirable to co-feed molecular hydrogen into the LPI conversion process using a catalyst composition based on an MFI zeolite to extend the service life of the catalyst composition, this is not required in the process of the present disclosure using a conversion catalyst composition based on a zeolite of the MEL framework type, due to its extremely low deactivation rate, even in the absence of co-fed molecular hydrogen. Thus, in a particularly advantageous embodiment of the aromatic hydrocarbon conversion process of the present disclosure, molecular hydrogen is not co-fed into the conversion reactor. Such elimination of hydrogen co-feeding, and thus elimination of hydrogen consumption from the conversion reactor, hydrogen supply lines, hydrogen compressors, and hydrogen recycle lines, greatly simplifies the process and system design, resulting in a reduction in the cost of system equipment and simpler and more reliable operation of the conversion process and conversion reactor.

[0128] The xylene loss ("Lx(1)") in the aromatic hydrocarbon conversion process of the present disclosure can be calculated as Lx(1) = 100% × (W1 - W2) / W1, where W1 is the total weight of all xylenes present in the aromatic hydrocarbon feed and W2 is the total weight of all xylenes present in the conversion product effluent. In certain embodiments of the aromatic hydrocarbon conversion process of the present disclosure, at 2.5 hours -1At a WHSV of 1.3 wt%, xylene losses can reach a level of ≤ 0.2 wt%, such as ≤ 0.15 wt%, ≤ 0.10 wt%, or even ≤ 0.05 wt%, which is significantly lower than a comparative process using a ZSM-5 based catalyst composition, as demonstrated in the following examples.

[0129] Since the isomerization reaction causes meta-xylene and / or ortho-xylene to be converted into para-xylene, the conversion product effluent from the conversion reactor can advantageously include para-xylene with a concentration higher than that of the aromatic hydrocarbon feed. The conversion product effluent can further include C9+ aromatic compounds and C7-aromatic compounds, which can be fed into the conversion reactor as impurities in the aromatic hydrocarbon feed or produced by side reactions in the conversion reactor. The generation of additional C9+ aromatic hydrocarbons and C7-aromatic hydrocarbons is usually associated with xylene losses and is therefore undesirable.

[0130] In certain embodiments of the aromatic hydrocarbon conversion process of the present disclosure, the process has a cycle time of at least 2.5 hours. -1 The invention relates to a catalyst composition having a WHSV of at most 3000 wt ppm, such as at most 1600 wt ppm, or at most 1000 wt ppm, of C9+ aromatic hydrocarbons, based on the total weight of the conversion product effluent. Such a C9+ aromatic hydrocarbon yield achievable by using a MEL framework type zeolite in the conversion catalyst composition, particularly at 2.5 hours, is preferably at least 0.1 wt ppm, such as at most 0.2 wt ppm, or at most 0.3 wt ppm, of C9+ aromatic hydrocarbons, based on the total weight of the conversion product effluent. -1 At low WHSVs of , this is significantly lower than the yield demonstrated in a comparative process using a ZSM-5 based zeolite in the catalyst composition.

[0131] In certain embodiments of the aromatic hydrocarbon conversion process of the present disclosure, the process has a cycle time of at least 5.0 hours. -1 ppm, or up to 800wt ppm, or up to 600wt ppm, or up to 500wtppm, based on the total weight of the conversion product effluent. Such C9+ aromatic hydrocarbon yields achievable by using a MEL framework type zeolite in the conversion catalyst composition, particularly at 5.0 hours -1 At low WHSVs of , this is significantly lower than the yield demonstrated in a comparative process using a ZSM-5 based zeolite in the catalyst composition.

[0132] In certain other embodiments of the aromatic hydrocarbon conversion process of the present disclosure, the process has a cycle time of at least 10 hours. -1 and exhibits a C9+ aromatic hydrocarbon yield of at most 1000wt ppm, e.g., at most 800wt ppm, or at most 700wt ppm, or at most 600wt ppm, or at most 500wt ppm, based on the total weight of the conversion product effluent.

[0133] In certain other embodiments of the aromatic hydrocarbon conversion process of the present disclosure, the process has a cycle time of at least 2.5 hours. -1 and exhibits a benzene yield of at most 1000 wt ppm, e.g., at most 800 wt ppm, or at most 700 wt ppm, or at most 600 wt ppm, or at most 500 wt ppm, based on the total weight of the conversion product effluent.

[0134] In certain other embodiments of the aromatic hydrocarbon conversion process of the present disclosure, the process has a cycle time of at least 5.0 hours. -1 The conversion product effluent has a WHSV of at most 800 ppm, e.g., at most 700 ppm, or at most 600 ppm, or at most 500 ppm, of benzene yield, based on the total weight of the conversion product effluent.

[0135] In certain other embodiments of the aromatic hydrocarbon conversion process of the present disclosure, the process has a cycle time of at least 10 hours. -1 and exhibiting a benzene yield of at most 500 ppm, such as at most 400 ppm, or at most 300 ppm.

[0136] In certain other embodiments of the aromatic hydrocarbon conversion process of the present disclosure, the process has a cycle time of at least 2.5 hours. -1 The invention also provides a WHSV of at most 800 ppm, such as at most 600 ppm, at most 500 ppm, or at most 300 ppm toluene yield.

[0137] In certain other embodiments of the aromatic hydrocarbon conversion process of the present disclosure, the process has a cycle time of at least 5.0 hours. -1 The invention also provides a WHSV of at most 200 ppm, such as at most 100 ppm, or at most 50 ppm toluene yield.

[0138] In certain other embodiments of the aromatic hydrocarbon conversion process of the present disclosure, the process has a cycle time of at least 10 hours. -1 The invention also provides a WHSV of at most 200 ppm, such as at most 100 ppm, or at most 50 ppm toluene yield.

[0139] As described above, an advantage of the aromatic hydrocarbon conversion process of the present disclosure using a conversion catalyst composition comprising a MEL framework-type zeolite is high para-xylene selectivity in the conversion product effluent produced by the conversion reactor, and in certain embodiments, even at high WHSV> 5 hours -1 , e.g. ≥ 10 hours -1 , even ≥15 hours -1In the present disclosure, "p-xylene selectivity" is defined as the concentration of p-xylene among all xylenes in the conversion product effluent. Therefore, in certain embodiments, when the aromatic hydrocarbon feed contains p-xylene at a concentration of ≤15 wt% (preferably ≤10 wt%, preferably ≤8 wt%, preferably ≤6 wt%, preferably ≤5 wt%, preferably ≤3 wt%, preferably ≤2 wt%) based on the total weight of xylene in the aromatic hydrocarbon feed, the aromatic hydrocarbon conversion process of the present disclosure is 2.5 hours. -1 The aromatic hydrocarbon conversion process of the present disclosure can be used to convert the aromatic hydrocarbons into a desired product at a WHSV of ≥20%, ≥21%, ≥22%, or ≥23%. Therefore, in certain embodiments, when the aromatic hydrocarbon feed contains p-xylene at a concentration of ≤15 wt% (preferably ≤10 wt%, preferably ≤8 wt%, preferably ≤6 wt%, preferably ≤5 wt%, preferably ≤3 wt%, preferably ≤2 wt%) based on the total weight of xylene in the aromatic hydrocarbon feed, the aromatic hydrocarbon conversion process of the present disclosure can be used to convert the aromatic hydrocarbons into desired product at a WHSV of ≥20%, ≥21%, ≥22%, or ≥23%. -1 In certain embodiments, when the aromatic hydrocarbon feed contains p-xylene at a concentration of ≤15 wt% (preferably ≤10 wt%, preferably ≤8 wt%, preferably ≤6 wt%, preferably ≤5 wt%, preferably ≤3 wt%, preferably ≤2 wt%) based on the total weight of xylene in the aromatic hydrocarbon feed, the aromatic hydrocarbon conversion process of the present disclosure can be used even at a WHSV of 10 hours. -1 In certain embodiments, when the aromatic hydrocarbon feed contains p-xylene at a concentration of ≤15 wt% (preferably ≤10 wt%, preferably ≤8 wt%, preferably ≤6 wt%, preferably ≤5 wt%, preferably ≤3 wt%, preferably ≤2 wt%) based on the total weight of xylene in the aromatic hydrocarbon feed, the aromatic hydrocarbon conversion process of the present disclosure can be used even at 15 hours. -1 At a WHSV of ≥20%, or ≥21%, or ≥22%, or ≥23%, para-xylene selectivity can still be exhibited. Such high para-xylene selectivity at high WHSV is not achievable in comparative processes using ZSM-5 based catalyst compositions and is particularly advantageous. The fact that the conversion process of the present disclosure using MEL framework zeolite in the catalyst composition can achieve such high para-xylene selectivity at high WHSV is completely unexpected and very surprising.

[0140] The aromatic hydrocarbon conversion process of the present disclosure may be characterized as an LPI process using a catalyst composition comprising a MEL framework-type zeolite.The conversion reactor may be referred to as an LPI reactor or an LPI unit.

[0141] The LPI method is more energy-efficient than the VPI method. On the other hand, the VPI method is more effective than the LPI method in converting ethylbenzene. Therefore, if the aromatic hydrocarbon feed undergoing isomerization conversion contains ethylbenzene in a considerable concentration, it may accumulate in a xylene loop that only includes an LPI unit without a VPI reactor (or a VPI unit), unless a portion of the feed is purged. The accumulation of ethylbenzene in the purge of the feed or the xylene loop is undesirable. Therefore, it may be desirable to simultaneously maintain an LPI unit and a VPI unit in an aromatic compound production complex. In this case, various amounts of aromatic hydrocarbon feeds with the same or different compositions can be used to feed the LPI and VPI units. In one embodiment, the LPI unit and the VPI unit are arranged in parallel so that they can receive aromatic feeds from a common source with substantially the same composition. In another embodiment, the LPI unit and the VPI unit can be operated in series such that the aromatic hydrocarbon feed is first fed to the LPI unit to achieve at least partial isomerization of the xylenes to produce an LPI effluent, which is fed to the VPI unit where additional xylene isomerization and ethylbenzene conversion occurs. Alternatively, the VPI unit can be a lead unit that receives an aromatic hydrocarbon feed and produces an ethylbenzene-depleted VPI effluent, which is fed to the LPI unit for further xylene isomerization reactions.

[0142] The present disclosure is further illustrated by the following non-limiting examples. Many modifications and variations are possible, and it is to be understood that within the scope of the appended claims, the present disclosure may be practiced otherwise than as specifically described herein.

[0143] The present disclosure is further illustrated by the following non-limiting examples. Example

[0144] In the following examples, "TBABr" stands for tetrabutylammonium bromide (templating agent), "XRD" stands for X-ray diffraction, "SEM" stands for scanning electron microscopy, "TEM" stands for transmission electron microscopy, "DI water" stands for deionized water, and "HSA" stands for high surface area (i.e., having ≥ 200 m 2 / g specific surface area), "LSA" stands for low surface area (i.e., having a specific surface area of ​​≤150 m 2 Unless otherwise indicated, all parts are by weight.

[0145] Crystallite size measurement

[0146] The measurement of crystallite (i.e., primary particle) size is carried out as follows. Several TEM photos of zeolite samples are taken, primary particles are identified and measured. For each primary particle with an aspect ratio greater than 1, the longest dimension is determined by drawing a line between the two points farthest apart at the edge of the particle. Then, the length of the primary particle along the 45 ° diagonal line with the longest dimension and passing through the midpoint of the longest dimension is measured as the particle size.

[0147] Total and mesopore surface areas measured by BET

[0148] The total BET and t-plot micropore surface areas were measured by nitrogen adsorption / desorption after degassing the calcined zeolite powder at 350° C. for 4 hours. The mesopore surface area (i.e., external surface area) was obtained by subtracting the t-plot micropores from the total BET surface area. More information on this method can be found, for example, in "Characterization of Porous Solids and Powders: Surface Area, Pore Size and Density", S. Lowell et al., Springer, 2004.

[0149] Alpha value

[0150] The alpha value is a measure of the cracking activity of the catalyst and is described in U.S. Pat. No. 3,354,078 and Journal of Catalysis, Vol. 4, p. 527 (1965); Vol. 6, p. 278 (1966) and Vol. 61, p. 395 (1980), each of which is incorporated herein by reference. The experimental conditions for the tests used herein included a constant temperature of 538° C. and a variable flow rate, as described in detail in Journal of Catalysis, Vol. 61, p. 395 (1980).

[0151] Example A1: With SiO~50 2 / Al 2 O 3 Synthesis of the first ZSM-11 zeolite with a molar ratio

[0152] Contains TBABr aqueous solution, Ultrasil TM Synthesis of SiO2 from a synthetic mixture of precipitated silica, aluminum sulfate sol, NaOH aqueous solution and ZSM-11 seed crystals 2 / Al 2 O 3 A first ZSM-11 zeolite material having a molar ratio of 50. The synthesis mixture has the following molar composition:

[0153] SiO 2 / Al 2 O3 ~55

[0154] H 2 O / SiO 2 ~14.2

[0155] OH - / SiO 2 ~0.14

[0156] Na + / SiO 2 ~0.25

[0157] TBABr / SiO 2 ~0.05

[0158] The mixture was stirred in an autoclave at 280°F (138°C) for 72 hours. The product was filtered, washed with DI water and dried at 250°F (120°C). Figure 1 The XRD pattern of the obtained crystals showed a typical pattern of ZSM-11 zeolite. Figure 2 The SEM image of the resulting crystals shown in indicates irregularly shaped agglomerates formed by crystallites, wherein the size of the crystallites is <50 nm. Figure 3 As shown, TEM images of the resulting crystals indicate that most of the crystallites (primary particles) have a size of ≤400 angstroms and an aspect ratio of ≤2. The resulting crystals exhibit a silica / alumina molar ratio of ∼50. A portion of the as-synthesized zeolite crystals was converted to the hydrogen form by three ion exchanges with ammonium nitrate solution at room temperature, followed by drying at 250°F (120°C) and calcination at 1000°F (540°C) for 6 hours. The hydrogen form zeolite was found to have an alpha value of 800, a hexane adsorption value of 98 mg / g, and a total surface area of ​​490 m 2 / g and an external surface area of ​​134m 2 / g.

[0159] Example A2: SiO 2 / Al 2 O 3 Synthesis of a second ZSM-11 zeolite with a molar ratio of 25

[0160] Contains TBABr aqueous solution, Ultrasil TM Synthesis of SiO2 from a synthetic mixture of precipitated silica, aluminum sulfate sol, NaOH aqueous solution and ZSM-11 seed crystals 2 / Al 2 O 3 A second ZSM-11 zeolite material having a molar ratio of 24.7. The synthesis mixture has the following molar composition:

[0161] SiO 2 / Al2 O 3 ~26

[0162] H 2 O / SiO 2 ~14.3

[0163] OH - / SiO 2 ~0.1

[0164] Na + / SiO 2 ~0.37

[0165] TBABr / SiO 2 ~0.05

[0166] The mixture was stirred in an autoclave at 280°F (138°C) for 72 hours. The product was filtered, washed with DI water and dried at 250°F (120°C). Figure 4 The XRD pattern of the obtained crystals showed a typical pattern of ZSM-11 zeolite. Figure 5 The SEM image of the resulting crystals shown in indicated irregularly shaped agglomerates formed by crystallites, wherein the size of the crystallites was <50 nm. Figure 6 The TEM image of the resulting crystals shown in indicates that the majority of the crystallites (primary particles) had a size of ≤400 angstroms and an aspect ratio of ≤2. The resulting crystals exhibited a silica / alumina molar ratio of 24.7. A portion of the as-synthesized zeolite crystals were converted to the hydrogen form by three ion exchanges with ammonium nitrate solution at room temperature, followed by drying at 250°F (120°C) and calcination at 1000°F (540°C) for 6 hours. The hydrogen form zeolite was measured to have an alpha value of 1300, a hexane adsorption value of 100 mg / g, a molecular weight of 461 m / s, and a molecular weight of 100 m / s. 2 / g total surface area and 158m 2 / g of external surface area.

[0167] Example A3: With SiO2~28 2 / Al 2 O 3 Synthesis of the third ZSM-11 zeolite

[0168] Contains TBABr aqueous solution, Ultrasil TM Synthesis of SiO2 from a synthetic mixture of precipitated silica, aluminum sulfate sol, NaOH aqueous solution and ZSM-11 seed crystals 2 / Al 2 O 3 A third ZSM-11 zeolite material having a molar ratio of 28. The synthesis mixture has the following molar composition:

[0169] SiO 2 / Al 2 O 3 ~29

[0170] H 2 O / SiO 2 ~13.6

[0171] OH - / SiO 2 ~0.1

[0172] Na + / SiO 2 ~0.31

[0173] TBABr / SiO 2 ~0.08

[0174] The mixture was stirred in an autoclave at 300°F (148.9°C) for 72 hours. The product was filtered, washed with DI water and dried at 250°F (120°C). Figure 7 The XRD pattern of the obtained crystals showed a typical pattern of ZSM-11 zeolite. Figure 8 The SEM images of the resulting crystals shown in show elongated shaped agglomerates formed from crystallites, wherein the crystallites typically have a size >50 nm. Fig. 9 The TEM image of the resulting crystals shown in indicates that the primary size of most of the crystallites (primary particles) is in the range of 50 to 200 nanometers, and the aspect ratio is ≤3. The resulting crystals exhibit a silica / alumina molar ratio of ~28. A portion of the as-synthesized zeolite crystals was converted to the hydrogen form by three ion exchanges with ammonium nitrate solution at room temperature, followed by drying at 250°F (120°C) and calcination at 1000°F (540°C) for 6 hours. The hydrogen form zeolite was measured to have an alpha value of >1200, a hexane adsorption value of 90 mg / g, a carbonyl adsorption value of 446 m / s, and a carbonyl adsorption value of 100 m / s. 2 / g total surface area and 90m 2 / g of external surface area.

[0175] Example A-C1 (Comparative Example): Synthesis of ZSM-5 Zeolite

[0176] SiO was synthesized from a mixture of n-propylamine sol, silica, aluminum sulfate sol, and NaOH aqueous solution according to the procedure described in U.S. Pat. No. 4,526,879. 2 / Al 2 O 3 ZSM-5 zeolite with a molar ratio of -26 and a crystallite size of -100 nm.

[0177] Part B: Preparation of Catalyst Compositions

[0178] Example B1: Preparation of a first catalyst composition comprising the ZSM-11 zeolite of Example A1 and an alumina binder

[0179] 80 parts (basic: calcined at 538°C) of the first ZSM-11 zeolite prepared in Example A1 were mixed with 20 parts of high surface area alumina and water in a grinder. The alumina had a surface area of ​​more than 250 m 2 / g surface area (basis: calcined at 538°C). The mixture was extruded and then dried at 121°C overnight. The dried extrudates were calcined in nitrogen at 538°C for 3 hours to decompose and remove the template TBABr. The extrudates calcined in this manner were then moistened with saturated air and exchanged with 1N ammonium nitrate to remove sodium (to a level of <500wppm Na). After the ammonium nitrate exchange, the extrudates were washed with DI water before drying to remove residual nitrate ions. The ammonium-exchanged extrudates were then dried at 121°C overnight and calcined in air at 538°C for 3 hours to obtain a hydrogen-form catalyst composition comprising hydrogen-form ZSM-11 and an alumina binder. The total surface area of ​​the catalyst composition was measured to be 452m 2 / g, with an external surface area of ​​178m 2 / g, the hexane adsorption value is 90.5mg / g and the α value is 430.

[0180] Example B2: Preparation of a second catalyst composition comprising the ZSM-11 zeolite of Example A3 and an alumina binder

[0181] 80 parts (benchmark: calcined at 538°C) of the third ZSM-11 zeolite material from Example A3 were mixed with 20 parts of high surface area HSA alumina (benchmark: calcined at 538°C) and water in a grinder. The mixture was extruded and then dried overnight at 121°C. The dried extrudates were calcined at 538°C in nitrogen for 3 hours to decompose and remove the template TBABr. The extrudates so calcined were then moistened with saturated air and exchanged with 1N ammonium nitrate to remove sodium (to a level of <500wppm Na). After the ammonium nitrate exchange, the extrudates were washed with DI water before drying to remove residual nitrate ions. The ammonium exchanged extrudates were dried overnight at 121°C and calcined in air at 538°C for 3 hours to obtain a hydrogen-form catalyst composition comprising hydrogen-form ZSM-11 and an alumina binder. The total surface area of ​​the hydrogen-form catalyst composition was measured to be 430 m 2 / g, with an external surface area of ​​157m 2 / g and α value is 1200.

[0182] Example B3: Preparation of a third catalyst composition comprising the ZSM-11 zeolite of Example A2 and an alumina binder

[0183] 80 parts (baseline: calcined at 538°C) of the second ZSM-11 zeolite from Example A2 were mixed with 20 parts of high surface area HSA alumina (baseline: calcined at 538°C) and water in a grinder. The mixture was extruded and then dried overnight at 121°C. The dried extrudates were then calcined in nitrogen at 538°C for 3 hours to decompose and remove the template TBABr. The extrudates so calcined were then moistened with saturated air and exchanged with 1N ammonium nitrate to remove sodium (to a level of <500wppm Na). After the ammonium nitrate exchange, the extrudates were washed with DI water before drying to remove residual nitrate ions. The ammonium exchanged extrudates were dried overnight at 121°C and calcined in air at 538°C for 3 hours to obtain a hydrogen-form catalyst composition comprising a hydrogen-form ZSM-11 zeolite and an alumina binder. The total surface area of ​​the hydrogen-form catalyst composition was measured to be 432 m 2 / g, with an external surface area of ​​200m 2 / g, the hexane adsorption value is 85.5 mg / g and the α value is 1000.

[0184] Example B4: Preparation of a fourth catalyst composition comprising the ZSM-11 zeolite of Example A2 and a silica binder

[0185] 80 parts (basic: calcined at 538° C.) of ZSM-11 zeolite from Example A2 were mixed with 20 parts of Ultrasil TM Silica and colloidal silica (silica basis: calcined at 538°C) and water were mixed in a grinder. The mixture was extruded and then dried overnight at 121°C. The dried extrudates were calcined in nitrogen at 538°C for 3 hours to decompose and remove the template TBABr. The extrudates calcined in this manner were then moistened with saturated air and exchanged with 1N ammonium nitrate to remove sodium (to a level of <500wppmNa). After the ammonium nitrate exchange, the extrudates were washed with DI water before drying to remove residual nitrate ions. The ammonium-exchanged extrudates were then dried overnight at 121°C and calcined in air at 538°C to obtain a hydrogen-form catalyst composition comprising a hydrogen-form ZSM-11 zeolite and a silica binder. The hexane adsorption value of the hydrogen-form catalyst composition was measured to be 80.7 mg / g, and the total surface area was 430 m 2 / g, with an external surface area of ​​181m 2 / g and α value is 1200.

[0186] Example B5: Preparation of a fifth catalyst composition comprising the ZSM-11 zeolite of Example A2 and a low surface area alumina binder

[0187] 80 parts (base: calcined at 538°C) of ZSM-11 zeolite from Example A2 were mixed with 20 parts of low surface area alumina (base: calcined at 538°C) and water in a grinder. The mixture was extruded and then dried overnight at 121°C. The dried extrudates were calcined at 538°C in nitrogen for 3 hours to decompose and remove the template TBABr. The extrudates calcined in this way were then moistened with saturated air and exchanged with 1N ammonium nitrate to remove sodium (to a level of <500wppm Na). After the ammonium nitrate exchange, the extrudates were washed with DI water before drying to remove residual nitrate ions. The ammonium exchanged extrudates were then dried overnight at 121°C and calcined in air at 538°C to obtain a hydrogen-form catalyst composition comprising a hydrogen-form ZSM-11 zeolite and an alumina binder. The hexane adsorption value of the hydrogen-form catalyst composition was measured to be 80.5 mg / g and the total surface area was 396 m 2 / g, with an external surface area of ​​148m 2 / g and α value is 930.

[0188] Example B6: Preparation of a sixth catalyst composition comprising the ZSM-11 zeolite of Example A2, MCM-49 zeolite and an alumina binder

[0189] 40 parts (baseline: calcined at 538°C) of ZSM-11 zeolite from Example A2 and 40 parts of MCM-49 crystals were mixed with 20 parts of high surface area HSA alumina (baseline: calcined at 538°C) and water in a grinder. The mixture was extruded and then dried overnight at 121°C. The dried extrudates were calcined at 538°C in nitrogen for 3 hours to decompose and remove the template TBABr. The extrudates calcined in this manner were then moistened with saturated air and exchanged with 1N ammonium nitrate to remove sodium (to a level of <500wppm Na). After the ammonium nitrate exchange, the extrudates were washed with DI water before drying to remove residual nitrate ions. The ammonium exchanged extrudates were then dried overnight at 121°C and calcined in air at 538°C for 3 hours to obtain a hydrogen-form catalyst composition comprising hydrogen-form ZSM-11, MCM-49 and an alumina binder. The total surface area of ​​the hydrogen-form catalyst composition was measured to be 467 m 2 / g, with an external surface area of ​​170m 2 / g, the hexane adsorption value is 86.5 mg / g and the α value is 880.

[0190] Example B7: Preparation of a Seventh Catalyst Composition Comprising the ZSM-11 Zeolite of Example A2, the ZSM-5 Zeolite of Example A-C1, and an Alumina Binder

[0191] 40 parts (base: calcined at 538°C) of ZSM-11 zeolite from Example A2 and 40 parts of ZSM-5 zeolite from Example A-C1 were mixed with 20 parts of high surface area HSA alumina (base: calcined at 538°C) and water in a grinder. The mixture was extruded and then dried overnight at 121°C. The dried extrudates were calcined at 538°C in nitrogen for 3 hours to decompose and remove the template TBABr. The extrudates calcined in this manner were then moistened with saturated air and exchanged with 1N ammonium nitrate to remove sodium (to a level of <500wppm Na). After the ammonium nitrate exchange, the extrudates were washed with DI water before drying to remove residual nitrate ions. The ammonium exchanged extrudates were then dried overnight at 121°C and calcined in air at 538°C for 3 hours to obtain a hydrogen-form catalyst composition comprising hydrogen-form ZSM-11, hydrogen-form ZSM-5 and an alumina binder. The total surface area of ​​the hydrogen-form catalyst composition was measured to be 422 m 2 / g, with an external surface area of ​​182m 2 / g, the hexane adsorption value is 84.9 mg / g and the α value is 1000.

[0192] Example B8: Preparation of an eighth catalyst composition by steam treating the second catalyst composition in Example B2

[0193] The second catalyst composition of Example B2 was steam treated at 700°F (371°C) for 3 hours and exhibited the following properties: 84.1 mg / g hexane adsorption, 350 m / s 2 / g total surface area and an α value of 800.

[0194] Example B9: Preparation of a ninth catalyst composition by steam treating the third catalyst composition in Example B3

[0195] The third catalyst composition of Example B3 was steam treated at 700°F (371°C) for 3 hours and exhibited the following properties: 78.5 mg / g hexane adsorption, 415 m / g 2 / g total surface area and an α value of 720.

[0196] Examples B-C1 (Comparative): Preparation of Comparative Catalyst Compositions Comprising ZSM-5 Zeolite and Alumina Binder

[0197] 80 parts (baseline: calcined at 538°C) of ZSM-5 zeolite from Example A-C1 were mixed with 20 parts of HSA alumina (baseline: calcined at 538°C) and water in a grinder. The mixture was extruded and then dried overnight at 121°C. The dried extrudate was calcined at 538°C in nitrogen for 3 hours to decompose and remove the template agent n-propylamine. The extrudate calcined in this way was humidified with saturated air and exchanged with 1N ammonium nitrate to remove sodium from the catalyst (to a level of <500wppm Na). After the ammonium nitrate exchange, the extrudate was then washed with DI water to remove residual nitrate ions and then dried. The ammonium exchanged extrudate was then dried overnight at 121°C and calcined in air at 538°C for 3 hours to obtain a hydrogen-form catalyst composition comprising hydrogen-form ZSM-5 and an alumina binder. The total surface area of ​​the hydrogen-form catalyst composition was measured to be 450m 2 / g, the hexane adsorption value is 90mg / g and the α value is 900.

[0198] Part C: LPI process in the presence of a catalyst composition

[0199] A series of catalyst compositions having comparable extrudate sizes prepared in the above examples in Part B were tested in the liquid phase isomerization process in Examples C1-C6 and C-C1 below. Each catalyst composition tested was first ground to 10 / 20 mesh. Then, 1 gram of the ground catalyst composition was loaded into an upflow tubular reactor. To remove moisture, the filled catalyst composition was then dried under flowing nitrogen, heated from room temperature to 240°C at 2°C / min, and then held at 240°C for 1 hour. The isomerization feed was then supplied to the reactor from the bottom inlet to contact the filled catalyst composition. Isomerization conditions were set at 265 psig (1827 kPa, gauge pressure) and 240°C and from 2.5 to 15 hours. -1 Varying WHSV. No molecular hydrogen was fed into the reactor. The isomerization feed had the following composition based on the total weight of the isomerization feed: 13 wt% ethylbenzene, 1.5 wt% C8-C9 non-aromatic compounds, 1.5 wt% p-xylene, 19 wt% o-xylene and 66 wt% m-xylene. The isomerization product mixture effluent leaving the reactor from the top was collected and analyzed for its composition. In the reported results, the p-xylene selectivity in the product is defined as the concentration of p-xylene among all xylenes in the isomerization product mixture effluent. The xylene loss (Lx (%)) is calculated as follows: Lx = 100% × (W1-W2) / W1, where W1 is the total weight of xylenes in the isomerization feed, and W2 is the total weight of xylenes in the isomerization product mixture effluent.

[0200] Examples C-C1 (Comparative): LPI in the presence of the catalyst composition of Examples B-C1

[0201] The catalyst compositions of Examples B-C1 above were tested, which comprised an HSA alumina binder and SiO having medium-sized crystallites and ∼26 2 / Al 2 O 3 The molar ratios of ZSM-5 zeolite. WHSV and results are included in Tables C-C1.

[0202] Table C-C1

[0203] <![CDATA[WHSV (hours -1 )]]> 2.5 5 10 15 Selectivity of p-xylene in the product (%) 23.7 22.6 19.4 16.6 Ethylbenzene conversion rate (%) 3.8 1.1 0.8 0.4 Benzene yield (wppm) 978 327 309 79 A9+ yield (wppm) 4212 497 ~0 ~0 Toluene yield (wt%) 0.20 0.06 0.03 0.02 Xylene loss (%) 0.23 0.06 0.01 0.02

[0204] Example C1: LPI in the presence of the catalyst composition of Example B3

[0205] The catalyst composition of Example B3 above was tested, which contained an HSA alumina binder and a SiO2 having small crystallites and ∼25 2 / Al 2 O 3 The results and reaction conditions are shown in Table 1.

[0206] Table I

[0207] <![CDATA[WHSV (hours -1 )]]> 2.5 5 10 15 Selectivity of p-xylene in the product (%) 23.6 23.6 22.8 21.3 Ethylbenzene conversion rate (%) 1.8 1.0 0.6 0.4 Benzene yield (wppm) 936 308 312 76 A9+ yield (wppm) 707 253 ~0 ~0 Toluene yield (wt%) 0.11 0.03 0.03 0.02 Xylene loss (%) 0.04 0.02 0.04 0.04

[0208] The catalyst composition of Example B3 above was tested, which contained an HSA alumina binder and a SiO2 having small crystallites and ∼25 2 / Al 2 O 3 The molar ratio of ZSM-11 zeolite. WHSV and the results are shown in Table 1.

[0209] According to the data in Tables C-C1 and I, the advantages of the catalyst composition of Example B3 over the comparative catalyst composition of Example B-C1 are numerous and significant: (i) at 2.5 and 5 hours -1 At a WHSV of 1.5 and 5 hours, the catalyst composition of Example B3 of the present invention resulted in much lower xylene losses; (ii) at 2.5 and 5 hours -1 At a WHSV of 1.5 and 5 hours, the catalyst composition of the invention of Example B3 resulted in a much lower A9+ yield; (iii) at 2.5 and 5 hours -1 The catalyst composition of the invention of Example B3 also resulted in a much lower toluene yield at a WHSV of ≥5 hours; and (iv) -1At a high WHSV of 5 hours, the inventive catalyst composition of Example B3 resulted in a much higher para-xylene selectivity in the product mixture effluent, showing a much higher isomerization activity than the comparative catalyst composition of Examples B-C1. In particular, the inventive ZSM-11-containing catalyst composition of Example B3 was more effective at WHSV ≥ 5 hours. -1 The catalyst compositions based on ZSM-5 are much better than those of Examples B-C1 and have a WHSV of ≥10 up to 15 hours. -1 This is mainly attributed to the much higher para-xylene selectivity at such high WHSV.

[0210] Since the catalyst compositions of Example B3 and Comparative Examples B-C1 all contain HSA alumina as a binder, this example clearly shows the advantages of ZSM-11 zeolite over ZSM-5 zeolite in catalyzing the LPI process, especially in the range of 2.5 to 5 hours. -1 of lower WHSV.

[0211] Example C2: LPI in the presence of the catalyst composition of Example B2

[0212] The catalyst composition of Example B2 above was tested, which contained an HSA alumina binder and SiO2 having medium-sized crystallites and ∼28 2 / Al 2 O 3 The molar ratios of ZSM-11 zeolite. WHSV and results are shown in Table II.

[0213] Table II

[0214] <![CDATA[WHSV (hours -1 )]]> 2.5 5 10 15 Selectivity of p-xylene in the product (%) 23.5 22.8 20.0 17.1 Ethylbenzene conversion rate (%) 1.9 1.1 0.6 0.5 Benzene yield (wppm) 902 482 ~0 ~0 A9+ yield (wppm) 2099 416 ~0 ~0 Toluene yield (wt%) 0.10 0.03 0.01 ~0 Xylene loss (%) 0.13 ~0 ~0 ~0

[0215] From the data in Tables C-C1 and II, the following advantages of the catalyst composition of the invention of Example B2 over the comparative catalyst composition of Example B-C1 can be observed: (i) at 2.5 and 5 hours -1 At a WHSV of 1.5 hours, the catalyst composition of Example B2 of the present invention resulted in much lower xylene losses; (ii) at 2.5 and 5 hours -1 At a WHSV of 1.5 and 5 hours, the catalyst composition of the invention of Example B2 resulted in a much lower A9+ yield; (iii) at 2.5 and 5 hours -1 The catalyst composition of the invention of Example B2 also resulted in a much lower toluene yield at a WHSV of ≥5 hours; and (iv) -1At a high WHSV of , the inventive catalyst composition of Example B2 resulted in a slightly higher para-xylene selectivity in the product mixture effluent, showing a slightly higher isomerization activity than the comparative catalyst composition of Examples B-C1. Therefore, the inventive catalyst composition of Example B2 is superior to the ZSM-5-based catalyst composition of Comparative Examples B-C1.

[0216] As can be seen from the data in Tables I and II, the catalyst composition of the invention of Example B2 resulted in a -1 Higher xylene losses under WHSV at 2.5 and 5.0 h -1 The A9+ yield was much higher at WHSV, and at 5 and 10 hours -1 The catalyst composition of Example B3 is superior to the catalyst composition of Example B2. It is believed that the smaller crystal size of the ZSM-11 zeolite in the catalyst composition of Example B3 leads to the higher performance of the catalyst composition. The ZSM-11 zeolite in these two catalysts has similar SiO 2 / Al 2 O 3 Molar ratio. Therefore, a ZSM-11 zeolite having a crystallite size of ≤ 80 nm, and more preferably ≤ 50 nm, and still more preferably ≤ 30 nm is preferred, especially for preparing an LPI isomerization catalyst composition.

[0217] Example C3: LPI in the presence of the catalyst composition of Example B1

[0218] The catalyst composition of Example B1 above was tested, which comprises an HSA alumina binder and a catalyst having small crystallites and SiO 2 / Al 2 O 3 ZSM-11 zeolite at a molar ratio of 50. The WHSV and results are shown in Table III.

[0219] Table III

[0220] <![CDATA[WHSV (hours -1 )]]> 2.5 5 10 15 Selectivity of p-xylene in the product (%) 23.6 22.3 18.5 15.2 Ethylbenzene conversion rate (%) 1.0 0.5 0.3 0.2 Benzene yield (wppm) 530 ~0 ~0 ~0 A9+ yield (wppm) 396 ~0 ~0 ~0 Toluene yield, wt% 0.03 0.01 ~0 ~0 Xylene loss (%) ~0 ~0 ~0 ~0

[0221] From the data in Tables C-C1 and III, the following advantages of the catalyst composition of the invention of Example B1 over the comparative catalyst composition of Examples B-C1 can be observed: (i) at 2.5 and 5 hours -1 At a WHSV of 1.5 hours, the catalyst composition of Example B1 resulted in much lower xylene losses; (ii) at 2.5 and 5 hours -1 At a WHSV of 1.5 hours, the catalyst composition of the invention of Example B1 resulted in a much lower A9+ yield; and (iii) at 2.5 and 5 hours -1At a WHSV of 1.3 %, the inventive catalyst composition of Example B1 also resulted in a much lower toluene yield. Therefore, the inventive catalyst composition of Example B1 is superior to the ZSM-5-based catalyst compositions of Comparative Examples B-C1.

[0222] It can be seen from the data in Table I and Table IV that the catalyst composition of Example B1 of the present invention has a high -1 The high WHSV of Example B3 resulted in a much lower para-xylene selectivity than the catalyst composition of the present invention of Example B3. Therefore, the catalyst composition of Example B3 is superior to the catalyst composition of Example B1. Although not wishing to be bound by a particular theory, it is believed that the much higher SiO2 content of the ZSM-11 zeolite in the catalyst composition of Example B1 2 / Al 2 O 3 The molar ratio results in a lower isomerization activity than the catalyst composition of Example B3. The ZSM-11 zeolites in the two catalyst compositions have comparable crystallite sizes. Therefore, particularly for the purpose of preparing an LPI isomerization catalyst composition, among the ZSM-11 zeolites, preferably the ZSM-11 zeolite has a SiO content of 20 to 40, and more preferably 20 to 30. 2 / Al 2 O 3 Molar ratio.

[0223] Example C4: LPI in the presence of the catalyst composition of Example B4

[0224] The catalyst composition of Example B4 described above was tested, which comprises a silica binder and a catalyst having small crystallites and SiO 2 / Al 2 O 3 ZSM-11 zeolite with a molar ratio of -25. The WHSV and results are shown in Table IV below.

[0225] Table IV

[0226] <![CDATA[WHSV (hours -1 )]]> 2.5 5 10 15 Selectivity of p-xylene in the product (%) 23.7 23.7 23.2 22.1 Ethylbenzene conversion rate (%) 1.9 0.9 0.6 0.3 Benzene yield (wppm) 1177 328 327 ~0 A9+ yield (wppm) 779 255 ~0 ~0 Toluene yield, wt% 0.07 0.03 0.03 0.01 Xylene loss (%) 0.02 0.03 0.04 0.01

[0227] From the data in Tables C-C1 and IV, the following advantages of the catalyst composition of the invention of Example B4 over the comparative catalyst composition of Example B-C1 can be observed: (i) at 2.5 and 5 hours -1 At a WHSV of 1.5 hours, the catalyst composition of Example B4 of the present invention resulted in much lower xylene losses; (ii) at 2.5 and 5 hours -1 At a WHSV of 1.5 and 5 hours, the catalyst composition of the invention of Example B4 resulted in a much lower A9+ yield; (iii) at 2.5 and 5 hours -1The catalyst composition of the invention of Example B2 also resulted in a much lower toluene yield at a WHSV of ≥5 hours; and (iv) -1 At a high WHSV of 5 hours, the inventive catalyst composition of Example B4 resulted in significantly higher para-xylene selectivity in the product mixture effluent, which showed significantly higher isomerization activity than the comparative catalyst composition of Examples B-C1. Therefore, the inventive catalyst composition of Example B4 is far superior to the ZSM-5-based catalyst composition of Comparative Examples B-C1. In particular, the inventive ZSM-11-containing catalyst composition of Example B4 has a significantly higher isomerization activity at WHSV ≥ 5 hours. -1 The catalyst compositions based on ZSM-5 are much better than those of Examples B-C1 and have a WHSV of ≥10 up to 15 hours. -1 This is mainly attributed to the much higher para-xylene selectivity at such high WHSV.

[0228] From the data in Table I and Table IV, it can be seen that the catalyst compositions of the present invention of Examples B3 and B4 have very similar performances in the LPI process test. This indicates that SiO 2 / Al 2 O 3 The same small crystallite ZSM-11 zeolite at a molar ratio of -25 can be combined with HSA alumina or silica to produce the high activity, high performance catalyst composition of the present disclosure.

[0229] Example C5: LPI in the presence of the catalyst composition of Example B5

[0230] The catalyst composition of Example B5 above was tested, which contained an LSA alumina binder and a catalyst having small crystallites and SiO 2 / Al 2 O 3 ZSM-11 zeolite at a molar ratio of -25. The WHSV and results are shown in Table V below.

[0231] Table V

[0232] <![CDATA[WHSV (hours -1 )]]> 2.5 5 10 15 Selectivity of p-xylene in the product (%) 23.7 23.5 22.7 21.2 Ethylbenzene conversion rate (%) 1.9 1.0 0.5 0.3 Benzene yield (wppm) 1051 600 ~0 ~0 A9+ yield (wppm) 1306 482 ~0 ~0 Toluene yield, wt% 0.08 0.02 ~0 ~0 Xylene loss (%) 0.06 ~0 ~0 ~0

[0233] From the data in Tables C-C1 and V, the following advantages of the catalyst composition of the invention of Example B5 over the comparative catalyst composition of Examples B-C1 can be observed: (i) at 2.5 and 5 hours -1 At a WHSV of 1.5 hours, the catalyst composition of the invention of Example B5 resulted in much lower xylene losses; (ii) at 2.5 and 5 hours -1 At a WHSV of 1.5 hours, the catalyst composition of Example B5 resulted in a much lower A9+ yield; (iii) at 2.5 and 5 hours -1The catalyst composition of the invention of Example B5 also resulted in a much lower toluene yield at a WHSV of ≥5 hours; and (iv) -1 At a high WHSV of 5 hours, the inventive catalyst composition of Example B5 resulted in significantly higher para-xylene selectivity in the product mixture effluent, which showed significantly higher isomerization activity than the comparative catalyst composition of Examples B-C1. Therefore, the inventive catalyst composition of Example B5 is far superior to the ZSM-5-based catalyst composition of Comparative Examples B-C1. In particular, the inventive ZSM-11-containing catalyst composition of Example B5 has a significantly higher isomerization activity at WHSV ≥ 5 hours. -1 The catalyst compositions based on ZSM-5 are much better than those of Examples B-C1 and have a WHSV of ≥10 up to 15 hours. -1 This is mainly attributed to the much higher para-xylene selectivity at such high WHSV.

[0234] From the data in Table I and Table V, it can be seen that the catalyst compositions of the present invention of Examples B3 and B5 have very similar performances in the LPI process test. This indicates that SiO 2 / Al 2 O 3 The same small crystallite ZSM-11 zeolite at a molar ratio of ~25 can be combined with HSA alumina or LSA alumina to produce the highly active, high performance catalyst compositions of the present disclosure. Nevertheless, the catalyst composition of Example B3 exhibits slightly higher performance than the catalyst composition of Example B5, particularly in terms of xylene selectivity at all WHSVs, selectivity at WHSVs of 2.5 and 5 hours. -1 The benzene yields at 2.5 and 5 h -1 This may be attributed to the higher surface area of ​​the alumina binder used in the catalyst composition of Example B3.

[0235] Example C6: LPI in the presence of the catalyst composition of Example B6

[0236] The catalyst composition of Example B6 above was tested, which contained an HSA alumina binder, a SiO 2 / Al 2 O 3 The molar ratios of ZSM-11 zeolite and MCM-49 zeolite. The WHSV and results are shown in Table VI below.

[0237] Table VI

[0238] <![CDATA[WHSV (hours -1 )]]> 2.5 5 10 15 Selectivity of p-xylene in the product (%) 23.6 23.0 20.2 17.4 Ethylbenzene conversion rate (%) 2.5 1.1 0.6 0.3 Benzene yield (wppm) 1290 334 350 86.6 A9+ yield (wppm) 1687 226 ~0 ~0 Toluene yield, wt% 0.17 0.03 0.02 0.02 Xylene loss (%) 0.16 0.02 0.04 0.03

[0239] From the data in Tables C-C1 and VI, the following advantages of the catalyst composition of Example B6 over the comparative catalyst composition of Example B-C1 can be observed: (i) at 2.5 and 5 hours -1 At a WHSV of 1.5 hours, the catalyst composition of Example B6 of the present invention resulted in much lower xylene losses; (ii) at 2.5 and 5 hours -1 At a WHSV of 5 hours, the catalyst composition of the invention of Example B6 resulted in a much lower A9+ yield; and (iii) at ≥5 hours -1 At a high WHSV of , the inventive catalyst composition of Example B5 resulted in a slightly higher para-xylene selectivity in the product mixture effluent, showing a slightly higher isomerization activity than the comparative catalyst composition of Examples B-C1. Therefore, the inventive catalyst composition of Example B5 is superior to the ZSM-5-based catalyst composition of Comparative Examples B-C1.

[0240] It can be seen from the data in Table I and Table VI that the catalyst composition of the present invention of Example B3 is superior to the catalyst composition of Example B6 in terms of xylene loss, toluene yield, A9+ yield, benzene yield and para-xylene selectivity, especially at 2.5 and 5 hours. -1 A9+ yield under WHSV, especially at ≥5 h -1 WHSV, especially at 10 and 15 hours -1 Compared to the catalyst composition of Example B3, the presence of 50 wt% MCM-49 in the zeolite mixture may have reduced xylene losses, toluene yield, A9+ yield, benzene yield and para-xylene selectivity, but appears to have improved EB conversion.

[0241] The compositions of the zeolites and catalyst compositions in the above examples and the relationship of the above examples are provided in Table VII below.

[0242] Some of the data in Tables C-C1 and I to VI are also plotted in Fig.10 , 11 and in the figure in 12.

[0243] Fig.10 The para-xylene selectivity as a function of WHSV is shown for all process examples C-C1 and C1 to C6. It can be clearly seen from this figure that the process of the present invention in Examples C1 (using the catalyst composition of Example B3), C2 (using the catalyst composition of Example B2), C4 (using the catalyst composition of Example B4), C5 (using the catalyst composition of Example B5) and C6 (using the catalyst composition of Example B6) increases from 2.5 to 15 hours. -1The process of Example C3 (using the catalyst composition of Example B1) exhibited consistently higher para-xylene selectivity than the comparative process of Examples C-C1 (using a ZSM-5-based catalyst composition) over the entire experimental WHSV range. Only the process of Example C3 (using the catalyst composition of Example B1) exhibited a consistently higher para-xylene selectivity than the comparative process of Examples C-C1 (using a ZSM-5-based catalyst composition) over the entire experimental WHSV range. -1 In particular, the methods of Examples C1, C4 and C5 showed lower para-xylene selectivity than the comparative methods in Examples C-C1 at 2.5-15 hours. -1 The catalyst compositions used in these examples, namely those in Examples B3, B4 and B5, respectively, are highly advantageous in high throughput, high WHSV liquid phase isomerization processes for converting xylenes.

[0244] Fig.11 The yield of A9+ (i.e., C9+ aromatics) as a function of WHSV is shown for all process examples C-C1 and C1 to C6. The production of A9+ due to side reactions is highly undesirable in C8 aromatic isomerization processes. It can be clearly seen from this figure that all of the inventive processes of Examples C1 to C6 have a yield of A9+ (i.e., C9+ aromatics) as a function of WHSV. -1 In the low WHSV range, the A9+ yield is always lower than that of the comparative method in Example C-C1. It is also worth noting that due to the WHSV test range, especially WHSV ≥ 10 hours -1 High para-xylene selectivity at Fig.10 The prominent methods C1, C4 and C5 are also Fig.11 This is shown at low WHSV at 2.5 and 5.0 hours. -1 Obviously, the catalyst compositions of Examples B3, B4 and B5 used in these exemplary methods have very low A9+ yields even at ≤ 5.0 hours. -1 A lower WHSV is also beneficial.

[0245] Fig.12 The xylene loss as a function of WHSV is shown for all process examples C-C1 and C1 to C6. Xylene loss due to side reactions is highly undesirable in a C8 aromatic isomerization process. It can be clearly seen from this figure that all of the inventive processes of Examples C1 to C6 have a WHSV of 2.5 to 5.0 hours. -1 In the low WHSV range of , the xylene loss is significantly lower than that of the comparative process in Example C-C1. It is also worth noting that Fig.10 and 11 The prominent methods C1, C4 and C5 are also Fig.12 This is shown at 2.5 and 5.0 hours -1Very low xylene losses at low WHSV. Clearly, from this additional perspective, the catalyst compositions of Examples B3, B4, and B5 used in these exemplary processes are effective even at ≤ 5.0 hours. -1 A lower WHSV is also beneficial.

[0246]

[0247] Example C7: Evaluation of Catalyst Aging in LPI Process

[0248] To evaluate catalyst aging, a catalyst composition of the invention consisting essentially of ZSM-11 zeolite and alumina binder corresponding to Example B3 above was tested according to the same procedure as in Examples C1 to C6 above, except that: (i) a larger downflow tubular reactor was used, in which ~30-40 grams of the catalyst composition was filled; (ii) the isomerization feed was fed from the top of the reactor; (iii) the isomerization product mixture effluent exited from the bottom of the reactor; and (iv) the WHSV was fixed at 5 hours. -1 The test reaction was allowed to proceed for a period of more than 20 days. For comparison, a comparative catalyst composition consisting essentially of ZSM-5 zeolite and alumina binder corresponding to Example B-C1 was evaluated under the same test conditions for a comparable period of time, except that the WHSV was fixed at 4 hours. -1 The catalyst deactivation rates for the two catalysts were calculated from the test data and are reported in Table VIII below. Catalyst deactivation was calculated as the change in para-xylene selectivity (i.e., S(pX)1-S(pX)2, where S(pX)1 is the initial para-xylene selectivity in the product mixture effluent and S(pX)2 is the final para-xylene selectivity in the product mixture effluent after one month on the stream). Therefore, the higher the monthly (S(pX)1-S(pX)2), the higher the decrease in para-xylene selectivity in one month and the faster the catalyst deactivation.

[0249] Table VIII

[0250] Catalyst composition (S(pX)1-S(pX)2) per month <![CDATA[WHSV (hours -1 )]]> Alumina-bonded ZSM-11 0.01% 5 Alumina-bonded ZSM-5 0.9% 4

[0251] The data in Table VIII clearly show that the alumina-bound ZSM-11 catalyst composition of the present invention exhibits much superior performance in terms of catalyst deactivation rate than the comparative ZSM-5-based catalyst composition. At comparable WHSV, the monthly para-xylene selectivity reduction caused by the catalyst composition of the present invention is almost two orders of magnitude lower than the para-xylene selectivity reduction of the comparative catalyst composition. This again clearly shows the advantages of catalyst compositions containing ZSM-11 zeolite over ZSM-5-based catalyst compositions, especially in liquid phase isomerization.

[0252] The present disclosure may also include the following non-limiting embodiments.

[0253] A1. A MEL framework-type zeolite material comprising a plurality of crystallites, wherein at least 75% of the crystallites have a crystallite size of at most 200 nanometers, preferably at most 180 nanometers, preferably at most 160 nanometers, preferably at most 150 nanometers, preferably at most 140 nanometers, preferably at most 120 nanometers, preferably at most 100 nanometers, preferably at most 80 nanometers, and more preferably at most 50 nanometers as determined by transmission electron microscopy image analysis.

[0254] A2. The zeolitic material of A1, wherein the crystallites have an aspect ratio of 1-5, preferably 1-3, and more preferably 1-2.

[0255] A3. The zeolitic material of A1 or A2 having a silica to alumina molar ratio of 10-60, preferably 15-50, and more preferably 20-30.

[0256] A4. The zeolite material of any one of A1-A3, having a molecular weight of 300-600 m 2 / g, preferably 400-500m 2 / g, and more preferably 400-475m 2 / g of BET total surface area.

[0257] A5. The zeolitic material of any one of A1-A4, having a mesopore area accounting for at least 15% of the total surface area, preferably at least 20% of the total surface area, and more preferably at least 25% of the total surface area.

[0258] A6. The zeolitic material of any one of A1-A5, wherein at least a portion of the crystallites are aggregated to form a plurality of agglomerates.

[0259] A7. The zeolite material of any one of A1-A6, further exhibiting one or more of the following properties:

[0260] (I) a hexane adsorption value of 90-110 mg / g; and

[0261] (II) α value of 500-3000.

[0262] A8. The zeolitic material of any of A1-A7, wherein the crystallites are substantially spherical in shape.

[0263] A9. The zeolitic material of any of A1-A6, wherein the crystallites are substantially rod-shaped in shape.

[0264] A10. The zeolitic material of any one of A1 to A9, which is as synthesized.

[0265] A11. The zeolitic material of any one of A1-A9, which is calcined.

[0266] B1. A method for producing a zeolite material according to any one of A1 to A11, the method comprising:

[0267] (I) forming a synthesis mixture from a silicon source, an aluminum source, an alkali metal (M) hydroxide, a structure directing agent (SDA) source selected from the group consisting of tetrabutylammonium ("TBA") compounds, water, and optionally seed crystals, wherein the synthesis mixture has an overall composition in the following molar ratios:

[0268]

[0269] (II) subjecting the synthesis mixture to crystallization conditions comprising heating the synthesis mixture at a temperature of 100° C. to 150° C. to form a reaction mixture comprising a solid material; and

[0270] (III) obtaining a zeolite material from the reaction mixture.

[0271] B2. The method of B1, wherein the silicon source is precipitated silica.

[0272] B3. The method of B1 or B2, wherein the aluminum source is sodium aluminate solution and / or aluminum sulfate solution.

[0273] B4. The method of any one of B1-B3, wherein the SDA source is selected from TBA hydroxide, TBA chloride, TBA fluoride, TBA bromide, alkyl diamines containing 7 to 12 carbon atoms, and mixtures and combinations thereof.

[0274] B5. The method of any one of B1-B4, wherein step (III) comprises:

[0275] (IIIa) filtering the reaction mixture to recover the solid material;

[0276] (IIIb) washing the solid material; and

[0277] (IIIc) Drying the washed solid material.

[0278] B6. The method of B5, wherein the method further comprises:

[0279] (IIId) subjecting the washed solid material or the dried and / or calcined solid material obtained from step (Ib) to an ion exchange treatment using an ammonium salt to at least partially remove the alkali metal cations M + to obtain an ion-exchanged solid material; and

[0280] (IIIe) calcining the ion-exchanged solid material at a temperature of at least 500° C. for at least 1 hour.

[0281] B7. The method of any one of B1-B6, further comprising:

[0282] (IV) mixing the zeolitic material obtained in step (III) with a binder, optionally, a second zeolitic material, optionally, a hydrogenation metal and optionally, water;

[0283] (V) forming the mixture obtained in step (IV) into a desired shape; and

[0284] (VI) drying and / or calcining the shaped mixture obtained in step (V) to obtain a catalyst comprising the zeolite material and a binder.

[0285] B8. The method of B7, wherein step (V) comprises extruding the mixture.

[0286] B9. The method of B7 or B8, further comprising the following steps between steps (V) and (VI):

[0287] (Va) exchanging the shaped mixture with an ammonium salt ion.

[0288] C1. A catalyst composition comprising the zeolitic material of any one of A1-A11.

[0289] C2. The catalyst composition of C1, which is substantially free of a binder.

[0290] C3. The catalyst composition of C1 further comprises a binder.

[0291] C4.C3 catalyst composition, wherein the binder is selected from alumina, silica, titania, zirconia, zircon, kaolin, other refractory oxides and refractory mixed oxides, and mixtures and combinations thereof.

[0292] C5. The catalyst composition of C4, wherein the binder is alumina and / or silica.

[0293] C6. The catalyst composition of any one of C1-C5, having one or more of the following shapes: cylinder, solid sphere, trilobate, quadrilobate and eggshell sphere.

[0294] C7. The catalyst composition of any one of C1-C6, further comprising a second zeolite selected from zeolites having 10- or 12-membered rings in their microcrystalline structure.

[0295] C8. The catalyst composition of any one of C1-C7, further comprising a second zeolite having a constraint index of 0.5-15, preferably 1-10.

[0296] C9. The catalyst composition of any one of C1-C8, further comprising an MFI framework type zeolite. C10. The catalyst composition of C9, wherein the MFI framework type zeolite is ZSM-5.

[0297] C11. The catalyst composition of any one of C1-C10, wherein the binder has a concentration of 0-90 wt%, such as 20-80 wt%, or 20-50 wt%, based on the total weight of the catalyst composition.

[0298] C12. The catalyst composition of any of C1-C11, wherein the zeolite material has a concentration of 10-100 wt%, such as 20-80 wt%, or 50-80 wt%, based on the total weight of the catalyst composition.

[0299] C13. The catalyst composition of any one of C1-C12, which is used for catalyzing the isomerization of C8 aromatic hydrocarbons.

[0300] D1. A process for converting a feedstock comprising C8 aromatic hydrocarbons, the process comprising:

[0301] (I) supplying the aromatic hydrocarbon feed to a conversion reactor; and

[0302] (II) contacting at least a portion of the C8 aromatic hydrocarbons in the liquid phase with a conversion catalyst composition comprising a MEL framework-type zeolite under conversion conditions to effect isomerization of at least a portion of the C8 aromatic hydrocarbons to produce a conversion product effluent.

[0303] D2. The method of D1, wherein the conversion catalyst composition comprises a MEL framework-type zeolite in a concentration of at least 50 wt %, based on the total weight of all zeolites present in the conversion catalyst composition.

[0304] D3. The method of D1 or D2, wherein the MEL framework-type zeolite is at least partially in hydrogen form.

[0305] D4. The method of any one of D1-D3, wherein the conversion catalyst composition is the catalyst composition of any one of B1-B9.

[0306] D5. The method of any one of D1-D4, wherein the conversion conditions include an absolute pressure sufficient to maintain the C8 hydrocarbons in the liquid phase, and one or more of the following:

[0307] a temperature of up to 300°C, preferably 100-300°C, preferably 150-300°C, for example 200-300°C, 200-280°C, 200-260°C, or 240-260°C; and

[0308] 0.5-20 hours-1 , preferably 2-15 hours -1 , and more preferably 2-10 hours -1 , and more preferably 5-10 hours -1 WHSV.

[0309] D6. The method of any one of D1-D6, further comprising supplying molecular hydrogen into the conversion reactor.

[0310] D7. The method of D6, wherein the amount of hydrogen fed to the conversion reactor is in the range of 4-250 ppm, based on the weight of the aromatic hydrocarbon feed.

[0311] D8. The method of D6 or D7, wherein the molecular hydrogen is at least partially dissolved in the liquid phase, preferably substantially completely dissolved.

[0312] D9. The method of any one of D1-D5, wherein no molecular hydrogen is fed into the conversion reactor.

[0313] D10. The method of any one of D1-D9, wherein at least one of the following items is satisfied:

[0314] (i) the feed contains at most 1000 ppm of C9+ aromatic hydrocarbons, based on the total weight of the feed;

[0315] (ii) the feed comprises at most 10,000 ppm of C7-aromatic hydrocarbons, based on the total weight of the feed; and

[0316] (iii) the feed comprises at most 15 wt% para-xylene, based on the total weight of C8 hydrocarbons in the feed.

[0317] D11. The method of any one of D1-D10, which exhibits a -1 Up to 0.2% xylene loss at a WHSV of 1.30 WHSV, calculated as the percentage reduction in weight of xylenes in the conversion product effluent compared to the feed, based on the total weight of xylenes in the feed.

[0318] D12. The method of any one of D1-D11, wherein the method has at least 2.5 hours -1 The process may comprise a C9+ aromatic hydrocarbon yield of at most 3000 wt ppm, e.g., at most 1600 ppm, or at most 1000 ppm, based on the total weight of the conversion product effluent.

[0319] D13. The method of any one of D1-D12, wherein the method has at least 5.0 hours -1The process comprises a WHSV of at most 1600 ppm, or at most 1000 ppm, of C9+ aromatic hydrocarbons, based on the total weight of the conversion product effluent.

[0320] D14. The method of any one of D1-D13, wherein the method has at least 10 hours -1 The process exhibits a C9+ aromatic hydrocarbon yield of at most 1000 ppm based on the total weight of the conversion product effluent.

[0321] D15. The method of any one of D1-D14, wherein the method has at least 2.5 hours -1 The method can include providing a WHSV of at most 1000 wt ppm, such as at most 700 ppm, or at most 500 ppm, of benzene yield, based on the total weight of the conversion product effluent.

[0322] D16. The method of any one of D1-D15, wherein the method has at least 5.0 hours -1 The method further comprises: providing a WHSV of at most 700 ppm, or at most 500 ppm, of benzene, based on the total weight of the conversion product effluent.

[0323] D17. The method of any one of D1-D16, wherein the method has at least 10 hours -1 The method comprises: obtaining a WHSV of at most 500 ppm benzene based on the total weight of the conversion product effluent.

[0324] D18. The method of any one of D1-D17, wherein the method has at least 2.5 hours -1 The method can include providing a toluene yield of at most 800 ppm by weight, such as at most 500 ppm, or at most 200 ppm, based on the total weight of the conversion product effluent.

[0325] D19. The method of any one of D1-D18, wherein the method has at least 5.0 hours -1 The method comprises: obtaining a toluene product having a WHSV of at most 200 ppm based on the total weight of the conversion product effluent.

[0326] D20. The method of any one of D1-D19, wherein the method has at least 10 hours -1 The method comprises: obtaining a toluene product having a WHSV of at most 200 ppm based on the total weight of the conversion product effluent.

[0327] D21. The method of any one of D1-D20, wherein the aromatic hydrocarbon feed contains p-xylene at a concentration of ≤15 wt% (preferably ≤10 wt%, preferably ≤8 wt%, preferably ≤6 wt%, preferably ≤5 wt%, preferably ≤3 wt%, preferably ≤2 wt%), based on the total weight of xylene in the aromatic hydrocarbon feed, and the method is carried out within 2.5 hours. -1 The invention also provides a method for producing a product having a para-xylene selectivity of at least 22%, preferably ≥ 23%, among the products of o-xylene, m-xylene and p-xylene at a WHSV of 1.0%.

[0328] D22. The method of D21, wherein the aromatic hydrocarbon feed contains p-xylene at a concentration of ≤15 wt% (preferably ≤10 wt%, preferably ≤8 wt%, preferably ≤6 wt%, preferably ≤5 wt%, preferably ≤3 wt%, preferably ≤2 wt%), based on the total weight of xylene in the aromatic hydrocarbon feed, and the method is carried out within 5 hours. -1 The invention further comprises a method for producing a product comprising: producing at least 20%, preferably ≥21%, preferably ≥22%, preferably ≥23% para-xylene selectivity among the products of o-xylene, m-xylene and p-xylene at a WHSV of .

[0329] D23. The method of D22, wherein the aromatic hydrocarbon feed contains p-xylene at a concentration of ≤15 wt% (preferably ≤10 wt%, preferably ≤8 wt%, preferably ≤6 wt%, preferably ≤5 wt%, preferably ≤3 wt%, preferably ≤2 wt%), based on the total weight of xylene in the aromatic hydrocarbon feed, and the method is carried out within 10 hours. -1 The invention further comprises a method for producing a product comprising: producing at least 20%, preferably ≥21%, preferably ≥22%, preferably ≥23% para-xylene selectivity among the products of o-xylene, m-xylene and p-xylene at a WHSV of .

[0330] D24. The method of D23, wherein the aromatic hydrocarbon feed contains p-xylene at a concentration of ≤15 wt% (preferably ≤10 wt%, preferably ≤8 wt%, preferably ≤6 wt%, preferably ≤5 wt%, preferably ≤3 wt%, preferably ≤2 wt%), based on the total weight of xylene in the aromatic hydrocarbon feed, and the method is carried out within 15 hours. -1 The invention further comprises a method for producing a product comprising: producing at least 20%, preferably ≥ 21%, of para-xylene among the products of o-xylene, m-xylene and p-xylene at a WHSV of .

[0331] D25. The method of any one of D1-D20, wherein the feed comprises 1-15 wt% ethylbenzene, based on the total weight of the feed.

[0332] E1. A process for converting a feedstock comprising C8 aromatic hydrocarbons, the process comprising:

[0333] (I) supplying the aromatic hydrocarbon feed to a conversion reactor; and

[0334] (II) contacting C8 aromatic hydrocarbons substantially in the liquid phase with a catalyst composition of any one of B1-B9 in a conversion reactor under conversion conditions to isomerize at least a portion of the C8 aromatic hydrocarbons to produce a conversion product effluent, wherein the conversion conditions include an absolute pressure sufficient to maintain the C8 hydrocarbons in the liquid phase, a temperature of 150-300°C and a WHSV of 2.5-15.

[0335] E2. The method of E1 further comprises supplying molecular hydrogen in an amount of 4-250 wppm into the conversion reactor, based on the total weight of the feed, wherein the hydrogen is substantially dissolved in the liquid phase.

[0336] E3. The process of E1 or E2, wherein no molecular hydrogen is fed into the conversion reactor.

[0337] E4. The method of any one of E1-E3, wherein at least one of the following items is satisfied:

[0338] (i) the feed contains at most 1000 ppm of C9+ aromatic hydrocarbons, based on the total weight of the feed;

[0339] (ii) the feed comprises at most 5000 ppm of C7-aromatic hydrocarbons, based on the total weight of the feed; and

[0340] (iii) the feed comprises at most 15 wt% para-xylene, based on the total weight of C8 hydrocarbons in the feed.

[0341] E5. The method of any one of E1-E4, wherein the aromatic hydrocarbon feed contains p-xylene at a concentration of up to 2 wt %, based on the total weight of xylene in the aromatic hydrocarbon feed and the method exhibits a reaction time of at least 2.5 hours. -1 Up to 0.5% xylene loss at a WHSV of 1.5 WHSV, calculated as the percentage reduction in weight of xylenes in the conversion product effluent compared to the feed based on the total weight of xylenes in the feed.

[0342] E6. The method of any one of E1-E5, wherein the aromatic hydrocarbon feed contains p-xylene at a concentration of ≤15 wt% (preferably ≤10 wt%, preferably ≤8 wt%, preferably ≤6 wt%, preferably ≤5 wt%, preferably ≤3 wt%, preferably ≤2 wt%), based on the total weight of xylene in the aromatic hydrocarbon feed, and the method is carried out within 2.5 hours. -1 The invention also provides a method for producing a product having a para-xylene selectivity of at least 22%, preferably ≥ 23%, among the products of o-xylene, m-xylene and p-xylene at a WHSV of 1.0%.

[0343] E7. The method of E6, wherein the aromatic hydrocarbon feed contains p-xylene at a concentration of ≤15 wt% (preferably ≤10 wt%, preferably ≤8 wt%, preferably ≤6 wt%, preferably ≤5 wt%, preferably ≤3 wt%, preferably ≤2 wt%), based on the total weight of xylene in the aromatic hydrocarbon feed, and the method is carried out within 5 hours. -1 The invention further comprises a method for producing a product comprising: producing at least 20%, preferably ≥21%, preferably ≥22%, preferably ≥23% para-xylene selectivity among the products of o-xylene, m-xylene and p-xylene at a WHSV of .

[0344] E8. The method of E7, wherein the aromatic hydrocarbon feed contains p-xylene at a concentration of ≤15 wt% (preferably ≤10 wt%, preferably ≤8 wt%, preferably ≤6 wt%, preferably ≤5 wt%, preferably ≤3 wt%, preferably ≤2 wt%), based on the total weight of xylene in the aromatic hydrocarbon feed, and the method is carried out within 10 hours. -1 The invention further comprises a method for producing a product comprising: producing at least 20%, preferably ≥21%, preferably ≥22%, preferably ≥23% para-xylene selectivity among the products of o-xylene, m-xylene and p-xylene at a WHSV of .

[0345] E9. The method of E8, wherein the aromatic hydrocarbon feed contains p-xylene at a concentration of ≤15 wt% (preferably ≤10 wt%, preferably ≤8 wt%, preferably ≤6 wt%, preferably ≤5 wt%, preferably ≤3 wt%, preferably ≤2 wt%), based on the total weight of xylene in the aromatic hydrocarbon feed, and the method is carried out within 15 hours. -1 The invention further comprises a method for producing a product comprising: producing at least 20%, preferably ≥21%, preferably ≥22%, preferably ≥23% para-xylene selectivity among the products of o-xylene, m-xylene and p-xylene at a WHSV of .

Claims

1. A process for converting an aromatic hydrocarbon feedstock containing C8 aromatic hydrocarbons, the process comprising: (I) supplying the aromatic hydrocarbon feed into a conversion reactor; and (II) contacting at least a portion of the C8 aromatic hydrocarbons in the liquid phase with a conversion catalyst composition comprising a first zeolite under conversion conditions in the conversion reactor to isomerize at least a portion of the C8 aromatic hydrocarbons to produce a conversion product effluent, wherein the first zeolite has a MEL framework type and comprises a plurality of crystallites, at least 75% of which have a crystallite size of at most 200 nanometers as determined by transmission electron microscopy image analysis, and wherein the conversion catalyst composition comprises a MEL framework type zeolite at a concentration of at least 50 wt%, based on the total weight of all zeolites present in the conversion catalyst composition, wherein the first zeolite has a silica to alumina molar ratio of 10 to 30.

2. The process according to claim 1, wherein the MEL framework-type zeolite is at least partially in hydrogen form.

3. The method according to claim 1, wherein the crystallites have an aspect ratio of 1-5.

4. The process according to claim 1, wherein the first zeolite material has a silica to alumina molar ratio of 10 to 60.

5. The method according to claim 1, wherein the first zeolite material has a molecular weight of 300-600 m 2 / g of BET total surface area.

6. The method of claim 1, wherein the first zeolite material has a mesopore surface area of ​​at least 15% of the total surface area.

7. The process according to claim 1, wherein the first zeolite is calcined.

8. The process according to claim 1, wherein the first zeolite is at least partially in the H-form.

9. The process according to claim 1, wherein the conversion catalyst composition further comprises a second zeolite material selected from zeolites having a 10- or 12-membered ring structure therein.

10. The process according to claim 1, wherein the conversion conditions include an absolute pressure sufficient to maintain the C8 aromatic hydrocarbons in the liquid phase, and one or more of: a temperature of up to 300°C; and 0.5-20 hours -1 WHSV.

11. The method of claim 1 further comprising supplying molecular hydrogen into the conversion reactor.

12. The process according to claim 11, wherein the amount of hydrogen fed into the conversion reactor is in the range of 4 to 250 ppm based on the weight of the aromatic hydrocarbon feed.

13. The process according to claim 12, wherein no molecular hydrogen is fed into the conversion reactor.

14. The method according to claim 1, which exhibits a -1 The invention provides a xylene loss of up to 0.2% at a WHSV of 1.3 WHSV, which is calculated as the percentage reduction in weight of xylenes in the conversion product effluent compared to the aromatic hydrocarbon feed based on the total weight of xylenes in the aromatic hydrocarbon feed.

15. The method according to claim 1, wherein the method has a duration of at least 2.5 hours. -1 The process comprises a WHSV of at most 3000 wt ppm of C9+ aromatic hydrocarbons, based on the total weight of the conversion product effluent.

16. The method according to claim 1, wherein the method has a duration of at least 5.0 hours. -1 The process comprises a WHSV of at most 1600 ppm of C9+ aromatic hydrocarbons, based on the total weight of the conversion product effluent.

17. The method according to claim 1, wherein the method has a duration of at least 10 hours. -1 The process comprises a WHSV of at most 1000 ppm of C9+ aromatic hydrocarbons, based on the total weight of the conversion product effluent.

18. The process according to claim 1, wherein the aromatic hydrocarbon feed contains p-xylene at a concentration of ≤ 15 wt %, based on the total weight of xylene in the aromatic hydrocarbon feed, and the process is carried out within 5 hours. -1 The invention also provides a method for producing a product having a para-xylene selectivity of at least 20% among o-xylene, m-xylene and p-xylene at a WHSV of 1.

08.

19. The process according to claim 1, wherein the aromatic hydrocarbon feed contains p-xylene at a concentration of ≤ 15 wt %, based on the total weight of xylene in the aromatic hydrocarbon feed, and the process is carried out within 10 hours. -1 The invention also provides a method for producing a product having a para-xylene selectivity of at least 20% among o-xylene, m-xylene and p-xylene at a WHSV of 1.

08.

20. A process for converting an aromatic hydrocarbon feedstock comprising C8 aromatic hydrocarbons, the process comprising: (I) supplying the aromatic hydrocarbon feed into a conversion reactor; and (II) contacting substantially C8 aromatic hydrocarbons in a liquid phase with a conversion catalyst composition in the conversion reactor under conversion conditions to isomerize at least a portion of the C8 aromatic hydrocarbons to produce a conversion product effluent, wherein the substantially C8 aromatic hydrocarbons in a liquid phase refer to ≥ 80 mol% of the C8 aromatic hydrocarbons remaining in the liquid phase, wherein the conversion conditions include an absolute pressure sufficient to substantially maintain the C8 aromatic hydrocarbons in the liquid phase, a temperature of 150-300° C., and a reaction time of 2.5-20 hours. -1 WHSV, wherein the conversion catalyst composition comprises a first zeolite material of a MEL framework type, the first zeolite material having a silica to alumina molar ratio of 20-40 and comprising a plurality of crystallites, at least 75% of the crystallites having a crystallite size of at most 200 nanometers as determined by transmission electron microscopy image analysis, and wherein the conversion catalyst composition comprises a MEL framework type zeolite at a concentration of at least 50 wt%, based on the total weight of all zeolites present in the conversion catalyst composition, wherein the first zeolite has a silica to alumina molar ratio of 10-30.

21. The method according to claim 20, wherein the first zeolite material has a silica to alumina molar ratio of 20 to 30.

22. The process according to claim 20 or claim 21, further comprising feeding molecular hydrogen into the conversion reactor in an amount of 4-250 wppm, based on the total weight of the feed, wherein > 80% of the molecular hydrogen is dissolved in the liquid phase.

23. A process according to claim 20 or claim 21 wherein no molecular hydrogen is fed into the conversion reactor.

Citation Information

Patent Citations

  • High meso-surface area, low Si / Al ratio pentasil zeolite

    US10010878B2

  • Xylene Isomerization Process and Catalyst Therefor

    US20110263918A1

  • Paraxylene Production Process and Apparatus

    US20110319688A1

  • Production of Paraxylene

    US20140350316A1

  • Process for the Production of Xylenes

    US20150376086A1